Surface-modified solid electrolytes, process for their preparation and their use in electrochemical cells
By depositing and rapidly heating the metal-based coating material on the surface of the solid electrolyte, the coated solid electrolyte is solved, and the problem of high interface resistance between the solid electrolyte and the lithium metal negative electrode is achieved, more stable lithium plating and extending the cycle life of the battery pack.
Patent Information
- Application Number
- CN202380053262.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-12
- Filing Date
- 2023-07-12
- Publication Date
- 2025-02-28
AI Technical Summary
The interface contact between the existing solid electrolyte and the lithium metal negative electrode has a high interface resistance, resulting in the growth of dendrite lithium and the short circuit of the battery pack.
A method of producing coated solid electrolytes is adopted by depositing a precursor powder of a metal-based coating material on the surface of the solid electrolyte and producing a molten metal-based coating material by rapid heating, which is then solidified to form a coated solid electrolyte.
The interface resistance between the solid electrolyte and the lithium metal negative electrode is significantly reduced, the uniformity of lithium plating and peeling is improved, the cycle stability of the battery pack is extended, and short circuits are avoided.
Smart Images

Figure CN119547249A_ABST
Abstract
Description
[0001] Related Applications
[0002] This application claims priority under applicable law to U.S. Provisional Application No. 63 / 368,165, filed on July 12, 2022, the contents of which are incorporated herein by reference in their entirety for all purposes. Technical Field
[0003] The present invention relates to the field of solid electrolytes and their use in electrochemical applications. More particularly, the present invention relates to solid electrolytes having at least one modified surface, methods for their manufacture and their use in electrochemical cells and batteries, in particular in all-solid-state batteries. Background Art
[0004] The growing demand for renewable energy requires the development of high-performance energy storage devices. Lithium-ion batteries (LIBs) are the main energy storage devices in portable electronic devices and have already dominated the electric vehicle market. However, existing LIBs with liquid electrolytes and graphite negative electrodes have reached their theoretical energy density limits (Choi, Jang Wook and Doron Aurbach. "Promise and reality of post-lithium-ion batteries with high energy densities." Nature Reviews Materials 1, no. 4 (2016): 1-16). One of the most promising strategies to further improve the energy density of LIBs is to replace the graphite negative electrode with lithium metal, which is widely regarded as the "holy grail" of battery development, and due to the hostless lithium storage mechanism of the lithium metal negative electrode, the capacity of the negative electrode can be increased tenfold.
[0005] The key challenge currently faced by lithium metal anodes is their unstable interface with liquid electrolytes, which leads to dendrite lithium growth and ultimately short circuits in the battery pack (Lin, Dingchang et al., "Reviving the lithium metal anode for high-energy batteries." Nature nanotechnology 12, no. 3 (2017): 194-206). It is generally believed that the use of solid electrolytes is one of the most promising solutions to inhibit dendrite growth due to their higher mechanical strength compared to traditional liquid electrolytes. All-solid-state lithium metal batteries (ASSLMBs) with solid electrolytes and lithium metal anodes have the potential to have much higher energy than traditional LIBs (Tikekar, Mukul D. et al., "Design principles for electrolytes and interfaces for stable lithium-metal batteries." Nature Energy 1, no. 9 (2016): 1-7).
[0006] However, the interface between the solid electrolyte and the lithium metal anode is quite different from its counterpart composed of liquid electrolyte (Liu, Bin et al., "Advancing lithium metal batteries." Joule 2.5 (2018): 833-845). For example, many solid electrolytes, including sulfide-based electrolytes (Lau, Jonathan et al., "Sulfide solid-state electrolytes for lithium battery applications." Advanced Energy Materials 8.27 (2018): 1800933), argyrodite-based electrolytes (Yu, Chuang et al., "Recent development of lithium argyrodite solid-state electrolytes for solid-state batteries: synthesis, structure, stability and dynamics." Nano Energy 83 (2021): 105858) and halide-based electrolytes (Li, Xiaona et al., "Progress and perspectives on halide lithium conductors for all-solid-state lithium batteries." Energy & Environmental Science 13.5 (2020): 1429-1461) are revealed to be electrochemically unstable to lithium reduction. A solid electrolyte interface (SEI) layer will be formed when contacting between the solid electrolyte and the lithium metal anode, resulting in elevated interfacial resistance and increased possibility of dendrite formation. Among all solid electrolytes, garnet-type solid electrolytes have a wide electrochemical stability window and are one of the few solid electrolytes that are stable at the electrochemical potential of lithium metal, making them excellent candidates for ASSLMBs (Thangadurai, Venkataraman et al., "Garnet-type solid-state fast Liion conductors for Li batteries: critical review." Chemical Society Reviews 43.13 (2014): 4714-4727).
[0007] Although garnet-type electrolytes paired with lithium metal anodes have theoretical stability, due to the Li 2 CO3 Due to surface contamination and the inherent lithium-phobic nature of garnet-type electrolytes, the interfacial contact between the two components is very poor in practice. It is widely reported that when garnet-type solid electrolytes are coupled with lithium metal anodes, the interfacial resistance can reach 1000Ωcm -2 Above (Wang, Chengwei et al., "Garnet-type solid-state electrolytes: materials, interfaces, and batteries." Chemical reviews 120.10 (2020): 4257-4300; Zhao, Ning et al., "Solid garnet batteries." Joule 3.5 (2019): 1190-1199; and Krauskopf, Thorben et al., "Lithium-metal growth kinetics on LLZO garnet-type solid-state electrolytes." Joule 3.8 (2019): 2030-2049). The large interfacial resistance causes severe voltage polarization during lithium plating / stripping cycles, resulting in the formation of dendritic lithium. Eventually, the dendritic lithium penetrates the grain boundaries of the electrolyte, causing internal short circuits and failure of the battery pack (Porz, Lukas et al., "Mechanism of lithium metal penetration throughinorganic solid-state electrolytes." Advanced Energy Materials 7.20(2017):1701003; and Ning, Ziyang et al., "Visualizing plating-induced cracking in lithium-anode solid-electrolyte cells." Nature Materials 20.8(2021):1121-1129). In order to solve the interfacial contact problem, various interfacial coatings have been developed in the past few years, but it remains a challenge to completely eliminate such interfacial resistance with simple, cost-effective and scalable technology. For example, an interfacial coating composed of germanium can reduce the interfacial resistance to 115Ωcm -2(Luo, W. et al., "Reducing Interfacial Resistance between Garnet-Structured Solid-State Electrolyte and Li-Metal Anode by a Germanium Layer." Adv. Mater 29 (2017): 1606042). A chemical treatment method using ammonium fluoride was used to remove surface contamination and generate a LiF coating, resulting in a 38.7Ωcm -2 The reduced interfacial resistance (Duan, Hui et al., "Building an air stable and lithium deposition regulable garnet interface from moderate-temperature conversion chemistry." Angewandte Chemie 132, no. 29 (2020): 12167-12173). The interfacial coating made of graphite has also been shown to reduce the interfacial resistance to 105Ωcm -2 (Shao, Yuanjun et al., "Drawing a softinterface: an effective interfacial modification strategy for garnet-typesolid-state Li batteries." ACS Energy Letters 3.6 (2018): 1212-1218).
[0008] The intermediate layer MoS has been revealed 2 The conversion reaction with lithium metal promotes interfacial wetting and reduces the interfacial resistance of garnet electrolyte to lithium to 14Ωcm -2 (Fu, Jiamin et al., "In situ formation of a bifunctional interlayer enabled by a conversion reaction to initiatively prevent lithium dendrites in a garnet solid-state electrolyte." Energy & Environmental Science 12.4 (2019): 1404-1412). So far, thin Al 2 O 3 The interfacial resistance of 1 Ω cm has been achieved by depositing the layer onto the surface of the garnet electrolyte.-2 The best performing interfacial coating (Han, Xiaogang et al., "Negating interfacial impedance in garnet-based solid-state Li metal batteries." Nature materials 16.5 (2017): 572-579).
[0009] However, there is still a need to develop new coating materials to protect the interface between the solid electrolyte and the anode, especially coating materials that offer advantages over conventional coating materials. Summary of the invention
[0010] According to one aspect, the present technology relates to a method for producing a coated solid electrolyte, the coated solid electrolyte comprising a metal-based coating deposited on at least a portion of a surface of the solid electrolyte, the method comprising the steps of:
[0011] (i) depositing a precursor powder of a metal-based coating material on at least a portion of a surface of a solid electrolyte;
[0012] (ii) subjecting a precursor powder of a metal-based coating material to a rapid heating process to produce a molten metal-based coating material; and
[0013] (iii) solidifying the molten metal-based coating material to produce the coated solid electrolyte.
[0014] In one embodiment, step (i) is performed by a mechanical or chemical coating method. In a related embodiment, step (i) is performed by a powder deposition technique. In a preferred embodiment, the powder deposition technique is a powder spreading technique, a powder friction technique or a powder dipping technique.
[0015] In another embodiment, the method further comprises the step of removing excess precursor powder of the metal-based coating material prior to step (ii).
[0016] In another embodiment, the rapid heating method is selected from Joule heating, microwave radiation, spark plasma sintering, induction heating, laser sintering, infrared radiation and electric pulse consolidation. In a related embodiment, the rapid heating method is Joule heating.
[0017] In another embodiment, the rapid heating process is carried out for a time of less than about 90 s, or less than about 80 s, or less than about 70 s, or less than about 60 s, or less than about 50 s, or less than about 40 s, or less than about 30 s, or less than about 25 s, or less than about 20 s, or less than about 15 s, or less than about 10 s.
[0018] In another embodiment, the rapid heating method is carried out for a time of about 1 s to about 90 s, or about 1 s to about 80 s, or about 1 s to about 70 s, or about 1 s to about 60 s, or about 1 s to about 50 s, or about 1 s to about 40 s, or about 1 s to about 30 s, or about 1 s to about 25 s, or about 1 s to about 20 s, or about 1 s to about 15 s, or about 1 s to about 10 s, or about 2 s to about 10 s, or about 3 s to about 10 s.
[0019] In another embodiment, the rapid heating process is carried out at a temperature in the range of about 550°C to about 1400°C, or about 600°C to about 1350°C, or about 650°C to about 1300°C, or about 700°C to about 1250°C, or about 700°C to about 1200°C.
[0020] In another embodiment, the rapid heating method is performed at about 5×10 2 ℃min -1 to about 1.44×10 4 ℃min -1 In a related embodiment, the rapid heating method is carried out at a heating temperature ramp rate in the range of about 3×10 3 ℃min -1 The heating temperature is ramped at a rate of 1.
[0021] In another embodiment, step (iii) is performed at about 5×10 2 ℃min -1 To about 4.8×10 3 ℃min -1 In a related embodiment, step (iii) is performed at a cooling temperature ramp rate in the range of about 3×10 3 ℃min -1 The cooling temperature is ramped at a rate of 1.
[0022] In another embodiment, the method further comprises the step of preparing a solid state electrolyte.
[0023] In another embodiment, the method further comprises the step of densifying the solid electrolyte. In a related embodiment, the densification step is performed by a rapid heating method. In a preferred embodiment, the rapid heating method is selected from Joule heating, microwave radiation, spark plasma sintering, induction heating, laser sintering, infrared radiation and electric pulse consolidation. In a more preferred embodiment, the rapid heating method is Joule heating.
[0024] According to another aspect, the present technology relates to a coated solid electrolyte obtained by a method as defined herein.
[0025] In one embodiment, the metal-based coating is uniformly deposited on the surface of the solid electrolyte. In an alternative embodiment, the metal-based coating is non-uniformly dispersed on the surface of the solid electrolyte.
[0026] In another embodiment, the metal-based coating material is selected from the group consisting of elemental metals, metal alloys, metal oxides, fluorinated metals, and combinations of at least two thereof.
[0027] In another embodiment, the metal-based coating material is a metallic element. In a related embodiment, the metallic element is selected from Al, Cu, Ag, Sn, Sb and Bi. In a preferred embodiment, the metallic element is Cu, Ag or Sn.
[0028] In another embodiment, the metal-based coating material is a metal alloy. For example, the metal alloy comprises a first metal component selected from the metal elements of the 14th and 15th groups of the periodic table and comprises a second metal component, wherein the second metal component is different from the first metal component. In a related embodiment, the first metal component is selected from Sn, Sb and Bi. In another related embodiment, the second metal component is an alkali metal, an alkaline earth metal, a transition metal, a post-transition metal, a metalloid or a lanthanide. For example, the second metal component is selected from Al, Mn, Co, Ni, Cu, Ag, Sn, Sb, La, Tb and Bi. In a preferred embodiment, the metal alloy is Sn-Mn, Sn-Co, Sn-Ni, Sn-Cu, Sn-Cu-Tb, Sn-Ag, Sn-La, Sn-Bi-Ag, Sb-Cu, Sb-Ag or Bi-Ag based alloy. In another preferred embodiment, the metal alloy is Cu 3 Sn or Cu 6 Sn 5 In another preferred embodiment, the metal alloy is AgSn x Bi 1-x , wherein x is 0≤x≤1. In a more preferred embodiment, the metal alloy is selected from AgSn, AgSn 0.8 Bi 0.2 、AgSn 0.6 Bi 0.4 、AgSn 0.4 Bi 0.6 and AgBi.
[0029] In another embodiment, the metal-based coating material is a metal fluoride. In a related embodiment, the metal fluoride is selected from SnF 2 、SnF 4 、ZnF2 、InF 3 , GaF 3 , SbF 3 , TlF, PbF 2 ,CuF 2 、BiF 3 , AlF 3 , AgF and LiF.
[0030] In another embodiment, the metal-based coating material is a metal oxide. In a related embodiment, the metal oxide is selected from SnO, SnO 2 , CuO, Cu 2 O.Bi 2 O 3 、Al 2 O 3 and Ag 2 O.
[0031] In another embodiment, the solid electrolyte is a ceramic solid electrolyte. In a related embodiment, the ceramic solid electrolyte is a garnet-type solid electrolyte. In a preferred embodiment, the garnet-type solid electrolyte is selected from Li 7 La 3 Zr 2 O 12 (LLZO), Li 6.25 Al 0.25 La 3 Zr 2 O 12 (Al-LLZO), Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 (LLZTO), Li 6.35 Al 0.05 La 3 Zr 2 Ta 0.5 O 12 (Al-LLZTO), Li 6.25 Nd 3 Zr 1.5 Ta 0.5 O 12 (LNZTO), Li 6.25 Sm 3 Zr 1.5 Ta 0.5 O 12 (LSZTO) and Li 6.25 (Sm 0.5 La 0.5 ) 3 Zr 1.5Ta 0.5 O 12 In a more preferred embodiment, the garnet-type solid electrolyte is selected from Li 7 La 3 Zr 2 O 12 (LLZO), Li 6.25 Al 0.25 La 3 Zr 2 O 12 (Al-LLZO), Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 (LLZTO) and Li 6.35 Al 0.05 La 3 Zr 2 Ta 0.5 O 12 (Al-LLZTO).
[0032] In another embodiment, the coated solid electrolyte further comprises at least one additional component. In a related embodiment, the additional component is selected from ion conductors, inorganic particles, glass or ceramic particles, nanoceramics, salts and other similar additives.
[0033] In another embodiment, the coated solid electrolyte further comprises a second coating material deposited on at least a portion of the opposite surface of the solid electrolyte. In a related embodiment, the second coating material is a coating material based on succinonitrile. For example, the coating material based on succinonitrile comprises a lithium salt.
[0034] According to another aspect, the present technology relates to an electrochemical cell comprising a negative electrode, a positive electrode and a coated solid electrolyte as defined herein.
[0035] In one embodiment, the metal-based coating of the coated solid electrolyte faces the negative electrode.
[0036] In another embodiment, the second coating material of the coated solid electrolyte, if present, faces the positive electrode.
[0037] In another embodiment, the negative electrode comprises an electrochemically active material comprising an alkali metal, an alkaline earth metal, an alloy containing at least one alkali metal or alkaline earth metal, a non-alkali metal and a non-alkaline earth metal, or an alloy or an intermetallic compound. In a related embodiment, the electrochemically active material of the negative electrode comprises lithium metal or an alloy thereof.
[0038] In another embodiment, the positive electrode comprises an electrochemically active material. In a related embodiment, the electrochemically active material of the positive electrode is selected from metal oxides, lithium metal oxides, metal phosphates, lithium metal phosphates, titanates, lithium titanates, metal fluorophosphates, lithium metal fluorophosphates, metal oxyfluorophosphates, lithium metal oxyfluorophosphates, metal sulfates, lithium metal sulfates, metal halides (e.g., fluorides), lithium metal halides (e.g., fluorides), sulfur, lithium sulfur, selenium, lithium selenium, and a combination of at least two thereof. For example, the metal of the electrochemically active material is selected from titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), zirconium (Zr), zinc (Zn), niobium (Nb), and a combination of at least two thereof.
[0039] In another embodiment, the positive electrode further comprises at least one electronically conductive material. In a related embodiment, the electronically conductive material is selected from carbon black, acetylene black, graphite, graphene, carbon fiber, carbon nanofiber, carbon nanotube, and a combination of at least two thereof.
[0040] In another embodiment, the positive electrode further comprises at least one binder. In a related embodiment, the binder is selected from the group consisting of a polyether type polymer binder, a fluorinated polymer, and a water soluble binder.
[0041] In another embodiment, the positive electrode further comprises at least one additional component. In a related embodiment, the additional component is selected from ion conductors, inorganic particles, glass or ceramic particles, nanoceramics, salts, and other similar additives.
[0042] According to another aspect, the present technology relates to a battery comprising at least one electrochemical cell as defined herein.
[0043] In one embodiment, the battery is selected from the group consisting of lithium batteries, lithium ion batteries, sodium batteries, sodium ion batteries, potassium batteries, potassium ion batteries, magnesium batteries and magnesium ion batteries. In a related embodiment, the battery is selected from the group consisting of lithium batteries or lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Schematic diagrams showing the following methods: (a) a method of preparing a solid-state electrolyte by a flash sintering method; and (b) a method of preparing a coated solid-state electrolyte by a melt quenching method according to a possible embodiment.
[0045] Figure 2 In the drawings, (a) is a schematic diagram of a rapid heating experimental setup according to one embodiment; (b) is a digital photograph showing the rapid heating experimental setup; and (c) is a graph of measured temperature vs. current passed through a graphite heating element.
[0046] Figure 3 The results show that the original LLZTO and AgSn 0.6 Bi 0.4 O x X-ray diffraction (XRD) pattern obtained for coated LLZTO as described in Example 2(a).
[0047] Figure 4 (a) shows the AgSn obtained before and after argon ion sputtering for 600 seconds. 0.6 Bi 0.4 O x X-ray photoelectron spectroscopy (XPS) measurement spectrum of LLZTO coating; (b) shows that the AgSn 0.6 Bi 0.4 O x Depth profile of the elemental composition near the surface coated with LLZTO; and (c) showing AgSn 0.6 Bi 0.4 O x Deconvoluted XPS fine spectra of Sn, Bi and Ag coated LLZTO as described in Example 2(b).
[0048] Figure 5 Shown are fresh and air-exposed AgSn recorded at different air exposure time intervals. 0.6 Bi 0.4 O x / LLZTO / AgSn 0.6 Bi 0.4 O x Electrochemical impedance spectroscopy (EIS) of the electrolyte was measured as described in Example 2(b).
[0049] Figure 6 Yes, pristine LLZTO and LLZTO / AgSn after contact with lithium metal 0.6 Bi 0.4 O x Schematic diagram of the difference in interface area between, as described in Example 2(b).
[0050] Figure 7 Scanning electron microscopy (SEM) images are shown, (a)-(c) show the original LLZTO surface (scale bars represent 20 μm, 5 μm and 1 μm, respectively), and (d) shows the AgSn 0.6 Bi 0.4 O x LLZTO surfaces were coated (scale bar represents 1 μm) as described in Example 2(c).
[0051] Figure 8 In (a), AgSn 0.6 Bi0.4 O x SEM image of a coated LLZTO surface; (b) shows an elemental mapping image of La, Zr, C, Ag, Sn, and Bi obtained by energy dispersive X-ray spectroscopy (EDS); and (c) a graph showing the results of EDS analysis obtained for the area outlined in (a), as described in Example 2(c). The scale bar represents 1 μm.
[0052] Fig. 9 In (a), AgSn 0.6 Bi 0.4 O x SEM image of a cross section of a coated LLZTO surface; and (b) shows an elemental mapping image of Zr, O, La, Bi, Sn and Ag obtained by EDS for the area outlined in (a), as described in Example 2(c). The scale bar represents 10 μm.
[0053] Fig.10 The display shows AgSn 0.6 Bi 0.4 O x Low magnification SEM image (a) and high magnification SEM image (b) of the interface between the coated LLZTO solid electrolyte and the lithium metal anode, as described in Example 2(c). The scale bars represent 10 μm and 2 μm, respectively.
[0054] Fig.11 In (a), AgSn 0.6 Bi 0.4 O x High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images of coated LLZTO nanoparticles; (b) shows the corresponding elemental mapping images of O, Zr, La, Ag, Sn, and Bi, respectively; (c) shows the 0.6 Bi 0.4 O x Atomic-resolution HAADF-STEM image taken near the edge of a coated LLZTO nanoparticle and its corresponding fast Fourier transform (FFT) map is shown in the inset; (d) shows the AgSn 0.6 Bi 0.4 O x
[0055] Coating the edges of LLZTO nanoparticles along (e) shows a high magnification HAADF-STEM image of the crystal zone axis; and (e) shows a FFT filtered HAADF-STEM image overlaid with yellow and blue false color images representing LLZTO and Bi-Sn alloy, respectively, as described in Example 2(d).
[0056] Fig.12 In the figure, (a) shows the Nyquist plot of a symmetric cell comprising LLZTO solid electrolyte coated with different Sn-based alloys; (b) shows an enlarged view of the Nyquist plot, showing the area representing the interface resistance; and (c) shows the Nyquist plot of a symmetric cell comprising LLZTO solid electrolyte coated with different Sb-based alloys, as described in Example 3(c).
[0057] Fig.13 Graph showing the rate performance of a symmetric cell comprising LLZTO solid-state electrolyte coated with different Sn and Sb-based coatings, as described in Example 3(d).
[0058] Fig.14 In the figure, (a) shows the Nyquist plots of a symmetric cell comprising an LLZTO solid electrolyte coated with an Ag-Sn alloy doped with different contents of Bi; (b) to (f) show the Nyquist plots of a symmetric cell comprising an AgSn alloy doped with y of 1, 0.8, 0.6, 0.4 and 0, respectively. 1- y Bi y O x Figure 2 shows the rate performance of symmetrical cells with LLZTO solid electrolytes coated with AgSn. 0.6 Bi 0.4 O x Symmetric cells coated with LLZTO solid electrolyte at 1 mA cm -2 / 1mAh cm -2 and 1.2 mA cm -2 / 0.1mAh cm -2 A graph of the cycling performance of the cells cycled at current density / capacity of , as described in Example 3(d).
[0059] Fig.15 Display, by Li / AgSn 0.6 Bi 0.4 O x -LLZTO-AgSn 0.6 Bi 0.4 O x / Li composition of the symmetrical battery cycling performance, (a) at 0.5 mA cm -2 The current density and 1 mAh cm -2 (b) at 0.5 mA cm -2 The current density and 0.1 mAh cm -2 (c) at 1 mA cm -2 The current density and 1 mAh cm -2 Under the area capacity ( Fig.14(g) is a magnified view of the last 5 cycles of the symmetric cell shown in (g), as described in Example 3(d).
[0060] Fig.16 (a) shows a Li / AgSn stacked stack that was stopped and disassembled for SEM analysis after 650 hours of cycling. 0.6 Bi 0.4 O x -LLZTO-AgSn 0.6 Bi 0.4 O x / Li composition of the symmetrical battery; (b) to (e) show that for the symmetrical battery obtained in (a), the cycling performance of the symmetrical battery in the presence of lithium and LLZTO / AgSn 0.6 Bi 0.4 O x SEM images recorded at a cross section of as described in Example 3(d). Scale bars represent 100 μm, 20 μm, 10 μm and 2 μm, respectively.
[0061] Fig.17 is a cross-sectional SEM image as described in Example 3(d), which shows poor contact between the lithium metal anode and the pristine LLZTO. The scale bar represents 20 μm.
[0062] Fig.18 In the figure, (a) and (b) show the representative results of AgSn 0.6 Bi 0.4 O x Specific capacity (mAh g) obtained by electrochemical cells coated with LLZTO solid electrolyte -1 ) and Coulombic efficiency (%) vs. number of cycles at C-rates between 0.1C and 1.0C; and (c) shows the corresponding charge-discharge curves obtained at different C-rates, as described in Example 3(d).
[0063] Fig.19 In (a), Li 2 AgSn 0.6 Bi 0.4 (a) is a schematic diagram of the diffusion path of lithium vacancies in; and (b) shows the corresponding diffusion barriers, as described in Example 3(e).
[0064] Fig. 20 Shown are LLZTO pellets before (a) and after densification (b); (c) digital photograph showing blue light emitted by the densified LLZTO electrolyte upon UV irradiation, as described in Example 6.
[0065] Fig.21, (a) presents the XRD patterns of the LLZTO solid electrolyte obtained before and after densification by rapid heating; (b) presents a SEM image showing the surface morphology of the LLZTO solid electrolyte, wherein the inset shows the particle size distribution diagram and digital photograph of the LLZTO solid electrolyte; (c) presents a Nyquist plot showing the bulk resistance of the LLZTO solid electrolyte tested with two blocked electrodes; (d) presents a portion of the periodic table indicating the relevant elements marked by orange squares, and the elements in their liquid, solid and gaseous forms at a temperature of 1100°C are marked in dark blue, light blue and green, respectively; (e) presents a Nyquist plot showing the interfacial resistance of LLZTO coated with materials based on Bi, Al, Cu, Sn and Sb; (f) presents a Nyquist plot showing the interfacial resistance of LLZTO coated with materials based on Cu, Sn and Cu-Sn (i.e., Cu 3 SnO X Nyquist plot of the interfacial resistance of LLZTO coated with Cu 3 SnO X Nyquist plot of the interfacial resistance of coated LLZTO at different treatment temperatures; (h) Contour plot showing the interfacial resistance between modified LLZTO and lithium metal at different Cu / Sn ratios and treatment temperatures, as described in Example 6.
[0066] Fig. 22 In the figure, (a) and (b) respectively present XRD patterns of Al-LLZO and Al-LLZTO solid electrolytes obtained before and after rapid densification; (c) and (d) respectively present SEM images of the surface morphology of Al-LLZO and Al-LLZTO solid electrolytes; and (e) and (f) respectively present graphs of the grain size distribution of Al-LLZO and Al-LLZTO solid electrolytes, as described in Example 6.
[0067] Fig.23 is the electrochemical impedance spectroscopy (EIS) spectrum recorded for a Li|LLZTO|Li symmetric cell as described in Example 6.
[0068] Fig.24 (a) shows Cu with a Cu:Sn molar ratio of 6:5 synthesized at different temperatures. 6 Sn 5 O x (a) presents EIS spectra of symmetrical cells comprising a coated LLZTO solid electrolyte; (b) presents EIS spectra comparing the interfacial resistance of symmetrical cells comprising garnet-type solid electrolytes with different Sn-based compositions, as described in Example 6.
[0069] Fig.25 The Cu on the surface of LLZTO is shown.z Sn y O x Low magnification SEM image (a) and high magnification SEM image (b) of the coating; (c) Cu was formed by melt quenching method z Sn y O x Schematic diagram of the mechanism of coating materials; (d) XRD spectra of original and modified LLZTO solid electrolytes; (e) XRD spectra of Cu z Sn y O x XPS spectra recorded of fresh and etched surfaces coated with LLZTO solid-state electrolyte; (f) XPS high-resolution spectrum of Sn 3d; (g) XPS high-resolution spectrum of Cu 2p, as described in Example 6.
[0070] Fig.26 , (a) is a high magnification SEM image showing the surface of the original LLZTO solid electrolyte; and (b) is a high magnification SEM image showing the morphology of the physical mixture of Cu and Sn obtained before the melt quenching process, as described in Example 6.
[0071] Fig. 27 EIS spectra tested in a symmetric cell as described in Example 6 are shown, (a) showing the increased interfacial resistance of uncoated LLZTO after exposure to air for 15 minutes, while (b) showing the interfacial resistance of fresh and exposed Cu 3 SnO x The curves obtained by coating LLZTO solid electrolyte are almost the same.
[0072] Fig.28 In the figure, (a) presents a plot of calculated Cu and Sn adsorption energies vs. number of layers; (b) presents a snapshot of an ab initio molecular dynamics (AIMD) simulation showing a side view of the interface between the Cu-Sn alloy coating and the LLZTO solid electrolyte; (c) and (d) present low and high magnification SEM images of the interface between freshly plated lithium and the Cu-Sn coated LLZTO solid electrolyte; and (e) presents an EDS elemental map of the same area, as described in Example 6.
[0073] Fig.29 (a) shows the Cu or Cu calculated by AIMD simulation and plotted against time. 3 (a) a graph showing the mean square displacement (MSD) of Cu and Sn atoms in Sn; and (b) a graph showing the charge density difference after Cu and Cu-Sn alloy are fully adsorbed on the surface of the LLZTO solid electrolyte, as described in Example 6.
[0074] Fig.30 In the case of Cu3 SnO x Voltage profiles of lithium stripping in a symmetric cell coated with LLZTO solid-state electrolyte, as described in Example 6.
[0075] Fig.31 is a high magnification SEM image of the lithium / pristine LLZTO interface obtained at a low accelerating voltage of 5 kV to enhance the contrast difference between lithium metal and the gap between lithium and LLZTO, as described in Example 6.
[0076] Fig.32 (a) and (b) show the Cu in symmetrical cells tested at room temperature and 60 °C, respectively. 3 SnO x Figure 2 shows the rate performance of the LLZTO-coated solid electrolyte; (c) and (d) show the rate performance of Cu in a symmetrical cell tested at room temperature and 60 °C, respectively. 3 SnO x Potential (V vs Li / Li) obtained by coating LLZTO solid electrolyte + ) vs. time (h); and (e) presents the results at 4 mA cm -2 Operando EIS spectrum of a symmetrical cell cycled at a current density of 200 Å at a temperature of 60° C., as described in Example 6.
[0077] Fig.33 Display from Fig.32 (c) and 32(d) are zoomed-in views of several typical cycles recorded at approximately 3000 h.
[0078] Fig.34 Presented at 0.2 mA cm -2 The original LLZTO, Sn-coated LLZTO and Cu were cycled at a current density of 6 Sn 5 Voltage curve of a symmetric cell coated with LLZTO solid-state electrolyte, as described in Example 6.
[0079] Fig.35In the figure, (a) presents a schematic diagram of the structure and composition of an all-solid-state electrochemical cell; (b) presents a Nyquist plot showing the impedance of an all-solid-state electrochemical cell having LFP and NMC positive electrodes, respectively; (c) presents a graph of capacity and efficiency vs. number of cycles at C-rates between 0.1C and 1.0C recorded for an all-solid-state electrochemical cell having an NMC positive electrode; (d) presents charge and discharge curves recorded at 1, 0.5, 0.2 and 0.1C for an all-solid-state electrochemical cell having an NMC positive electrode; and (e) presents a graph of capacity and efficiency vs. number of cycles recorded at 1C for an all-solid-state electrochemical cell having an NMC positive electrode, as described in Example 6.
[0080] Fig.36 In the figure, (a) shows the capacity and efficiency vs. cycle number recorded at 0.2C; (b) shows the capacity and efficiency vs. cycle number recorded at 0.2C for a LFP cathode and Cu 3 SnO x Capacity and efficiency vs. cycle number at C-rates between 0.1C and 1.0C recorded for an all-solid-state electrochemical cell coated with LLZTO solid-state electrolyte; and (c) presents the corresponding charge and discharge curves recorded at 1, 0.5, 0.2 and 0.1C, as described in Example 6.
[0081] Fig.37 Presented are graphs of capacity and efficiency vs. cycle number recorded at 1C for a conventional liquid cell comprising an NMC cathode, as described in Example 6.
[0082] Fig.38 XRD patterns of pristine LLZTO(Z) and LLZTO(LZ) solid-state electrolytes prepared from different metal oxide precursors by Joule heating technique, as described in Example 7, are presented.
[0083] Fig.39 SEM images of the surfaces of pristine LLZTO(Z) and LLZTO(LZ) solid-state electrolytes prepared from different metal oxide precursors by Joule heating technique, as described in Example 7, are presented.
[0084] Fig.40 Presented are the EIS spectra of pristine LLZTO(Z) and LLZTO(LZ) solid-state electrolytes prepared from different metal oxide precursors by Joule heating technique, as described in Example 7.
[0085] Fig.41 Presented by different Sn:SnF 2 Ratio of Sn:SnF prepared by Joule heating technique 2 EIS spectrum of coated LLZTO (LZ) solid electrolyte, as described in Example 8.
[0086] Fig.42 The original LLZTO (LZ) solid electrolyte prepared by Joule heating technique in Examples 7 and 8 and the Sn:SnF 2 (10:3) EIS spectrum of coated LLZTO (LZ) solid electrolyte.
[0087] Fig.43 The results show that the symmetrical cells with different Sn:SnF 2 Li / Sn-SnF with ratio (10:0.5, 10:1, 10:2, 10:3, 10:4, 10:5) 2 -LLZTO-Sn-SnF 2 / Li rate performance (step size: 0.2 mA cm -2 / 6 minutes). DETAILED DESCRIPTION
[0088] The following detailed description and examples are exemplary and should not be construed as further limiting the scope of the present invention. On the contrary, it is intended to cover all alternatives, modifications and equivalents that may be included as defined in this specification. By reading the following non-limiting description and with reference to the accompanying drawings, the purpose, advantages and other features of the solid electrolyte of the present invention, system, method and use thereof will be more obvious and better understood.
[0089] All technical and scientific terms and expressions used herein have the same definitions as commonly understood by those skilled in the art when relating to this technology. Nevertheless, for the sake of clarity, definitions of some terms and expressions used herein are provided below.
[0090] When the term "about" is used herein, it means approximately, around, or in the vicinity. For example, when the term "about" is used with respect to a numerical value, it modifies the numerical value to, for example, a 10% variation above and below its nominal value. This term can also take into account the rounding of numerical values or the probability of random error in experimental measurements, such as due to equipment limitations.
[0091] When numerical ranges are mentioned herein, the lower and upper limits of the range are always included in the definition unless otherwise stated. When numerical ranges are mentioned in this application, all intermediate ranges and subranges as well as individual values included in these ranges are intended to be included.
[0092] It is worth mentioning that throughout the following specification, when the article "a" is used to introduce an element, it does not have the meaning of "only one", but means "one or more". It is to be understood that when the specification indicates that a specific step, component, element or feature "may" or "can" be included, the specific component, element or feature does not need to be included in all alternatives.
[0093] Solid-state electrolytes, methods and systems for their production, and their use in electrochemical cells and batteries, such as in all-solid-state metal batteries, are described herein.
[0094] The present technology relates to a method for producing a coated solid electrolyte, the coated solid electrolyte comprising a metal-based coating deposited on at least a portion of the surface of the solid electrolyte. More particularly, the method comprises the steps of:
[0095] (i) depositing a precursor powder of a metal-based coating material on at least a portion of a surface of a solid electrolyte;
[0096] (ii) subjecting a precursor powder of a metal-based coating material to a rapid heating process to produce a molten metal-based coating material; and
[0097] (iii) solidifying the molten metal-based coating material to produce the coated solid electrolyte.
[0098] It is to be understood that the methods as described herein rely on thermal treatment techniques, rapid sintering techniques or melt quenching techniques.It is to be understood that the term "rapid heating method" refers to the entire thermal treatment process, which may include, for example, heating, dwelling and cooling steps.
[0099] According to one example, the step of depositing a precursor powder of a metal-based coating material on at least a portion of the surface of the solid electrolyte may be performed by any compatible method. The deposition step may be performed by a mechanical or chemical coating method.
[0100] For example, the deposition step can be performed by a powder deposition technique. The powder deposition technique can be, for example, a powder spreading technique, a powder friction technique, or a powder impregnation technique. However, various other methods can be used to apply the precursor powder of the metal-based coating material on the surface of the solid electrolyte.
[0101] According to another example, the precursor powder of the metal-based coating material may be attached to the surface of the solid electrolyte by attractive forces such as van der Waals forces.
[0102] According to another example, the method optionally further includes a step of removing excess metal-based coating material precursor powder before subjecting the metal-based coating material precursor powder to the rapid heating method. The step of removing excess metal-based coating material precursor powder can be performed by any compatible method. For example, compressed gas can be used to simply blow off excess metal-based coating material precursor powder.
[0103] According to another example, the rapid heating method can be performed by any compatible method. For example, the rapid heating method can be selected from Joule heating, microwave radiation, spark plasma sintering, induction heating, laser sintering, infrared radiation and electric pulse consolidation. According to a related example, the rapid heating method is Joule heating (also known as resistive heating, resistance heating or Ohm heating).
[0104] It is to be understood that the precursor powder of the metal-based coating material is subjected to a rapid heating process at a time, temperature, and temperature ramp rate sufficient to melt at least one component of the precursor powder of the metal-based coating material.
[0105] According to another example, the rapid heating method can be performed for a time less than about 90s. For example, the rapid heating method can be performed for a time less than about 80s, or less than about 70s, or less than about 60s, or less than about 50s, or less than about 40s, or less than about 30s, or less than about 25s, or less than about 20s, or less than about 15s, or less than about 10s. Alternatively, the rapid heating method can be performed for a time of about 1s to about 90s, including limits. For example, the rapid heating method can be performed for a time of about 1s to about 80s, or about 1s to about 70s, or about 1s to about 60s, or about 1s to about 50s, or about 1s to about 40s, or about 1s to about 30s, or about 1s to about 25s, or about 1s to about 20s, or about 1s to about 15s, or about 1s to about 10s, or about 2s to about 10s, or about 3s to about 10s, including limits. According to a related example, the rapid heating method can be performed for about 3 seconds.
[0106] According to another example, the rapid heating method may be performed at a temperature in the range of about 550° C. to about 1400° C., including limits. For example, the rapid heating method may be performed at a temperature in the range of about 600° C. to about 1350° C., or about 650° C. to about 1300° C., or about 700° C. to about 1250° C., or about 700° C. to about 1200° C., including limits.
[0107] According to another example, the rapid heating method can be performed at about 5×10 2 ℃min -1 to about 1.44×10 4 ℃min -1 The heating temperature ramp rate is carried out at a certain temperature, including the limit. For example, the rapid heating method can be carried out at a temperature of about 3×10 3 ℃min -1Alternatively, the rapid heating method may be isothermal and may be performed at a constant heating temperature. Alternatively, the rapid heating method may have a very short initial heating ramp, for example, heating from ambient temperature to the final temperature in as little as about 0 s. Alternatively, the rapid heating method may include at least one heating temperature ramp and at least one isothermal heating cycle.
[0108] According to another example, the curing step can be performed by any compatible method. According to a related example, the curing step can be a rapid quenching step or a rapid cooling step to form a substantially uniform metal-based coating on the surface of the solid electrolyte. For example, the curing step can be performed at about 5×10 2 ℃min -1 To about 4.8×10 3 ℃min -1 The cooling temperature ramp rate is carried out within a range of , including the limit. For example, the curing step can be carried out at a temperature of about 3×10 3 ℃min -1 Alternatively, the curing step may be isothermal and may be performed at a constant cooling temperature. Alternatively, the curing step may have a very short initial cooling temperature ramp, for example, cooling from the first temperature to ambient temperature in as little as about 0 s. Alternatively, the curing step may include at least one cooling temperature ramp and at least one isothermal cooling cycle.
[0109] According to another example, the method optionally further comprises a step of preparing a solid electrolyte before step (i). Any compatible method for preparing a solid electrolyte is considered. In some examples, the solid electrolyte is a garnet-type solid electrolyte and can be obtained by conventional solid-state synthesis or by fast sintering technology.
[0110] For example, the solid electrolyte powder precursor can be weighed to obtain the desired solid electrolyte. The raw powders can then be substantially uniformly mixed, such as by ball milling at a speed of about 300 rpm, for example, for about 10 hours. After mixing, the raw powders can be pressed into pellets and annealed, such as by rapid heating or annealing in a muffle furnace at a temperature of about 900° C. for about 12 hours.
[0111] According to another example, the method optionally further includes a step of densifying the solid electrolyte. The densification step can be performed by any compatible method. For example, the densification step can be performed by a thermal treatment technique to significantly improve the final pellet density. For example, the densification step can be performed by a rapid heating method such as Joule heating, microwave radiation, spark plasma sintering, induction heating, laser sintering, infrared radiation, and electric pulse consolidation. For example, the rapid heating method can be performed under the above conditions. According to a related example, the densification step can be performed by Joule heating, for example, for about 10 seconds.
[0112] To understand this technology in more detail, first refer to Figure 1 , which provides in (a) a schematic diagram of a method for producing a pristine solid-state electrolyte, and in (b) a schematic diagram of a method for producing a coated solid-state electrolyte according to a possible embodiment.
[0113] like Figure 1 As shown in (b), the deposition step can be carried out by a powder coating method, which involves spreading a metal-based coating material precursor powder on at least a portion of the surface of the solid electrolyte. The solid electrolyte can then be transferred to a rapid melting quenching device, wherein the surface coated with the metal-based coating material precursor powder faces upward. The metal-based coating material precursor powder can then be subjected to rapid heating to substantially melt at least one component of the precursor powder of the metal-based coating material to form a molten metal-based coating material. The molten metal-based coating material can be substantially or completely distributed over the surface of the solid electrolyte. The molten metal-based coating material can then be subjected to rapid cooling, thereby solidifying the molten metal-based coating material to produce a coated solid electrolyte.
[0114] According to another example, the method optionally further comprises a step of depositing a second coating material on at least a portion of the opposite surface of the solid electrolyte to form a second coating. It is understood that the second coating is deposited on a surface opposite to the surface of the solid electrolyte on which the metal-based coating is deposited.
[0115] Reference now Figure 2 (b) provides a digital photo of a rapid heating device for producing a raw solid electrolyte and / or a coated solid electrolyte according to a possible embodiment. The device for producing a raw solid electrolyte and / or a coated solid electrolyte by a rapid heating method needs to be able to provide a relatively high temperature environment with a relatively high heating and cooling rate. Any compatible device is considered.
[0116] A laboratory-scale rapid heating device was constructed by modifying a previously reported ultrafast high-temperature sintering device (Wang, Chengwei et al., "A general method to synthesize and sinter bulk ceramics in seconds." Science 368.6490 (2020): 521-526). All heat treatments disclosed in this disclosure were performed using a laboratory-scale rapid heating device. Figure 2 As shown in (b), the rapid heating device may include a pyrometer (1), a heating chamber with a rubber sealing O-ring (2), electrical connections (3), a gas inlet / outlet (4), a heating element (5), a transducer (6) and a power supply (7).
[0117] Still reference Figure 2 (b) Consider any suitable heating element (5) through which an electric current is passed through a conductor causing the temperature to rise. For example, a sheet of graphite can be an effective heating element. To prevent oxidation of the graphite, the heating element can be placed in an airtight chamber filled with an inert gas such as argon or nitrogen. The current can be supplied by a programmable power supply, and the temperature of the heating element can be controlled by varying the amplitude of the current. A pyrometer can be mounted on the top of the chamber to measure the temperature, and the infrared light emitted from the heating element can be captured by the pyrometer and converted to temperature. The temperature of the heating element depends on equation 1, where Q is the Joule heat and Q loss represents the amount of heat transferred from the heating element to the environment, I and R represent the current and resistance of the graphite heating element, respectively, A is the surface area of the graphite heating element, ε and σ are the emissivity and Stefan-Boltzmann constant, respectively, h is the heat transfer coefficient, T is the actual temperature of the heating element, and T 0 is the ambient temperature.
[0118]
[0119] If the heating element is operated at a relatively high temperature, the effect of heat radiation becomes much greater than heat conduction and convection. Therefore, the temperature of the heating element can be approximated by Equation 2, where the actual temperature of the heating element is proportional to the square root of the current, and the measured temperature is consistent with the theoretical prediction ( Figure 2 (c)).
[0120]
[0121] According to another example, the method as defined herein can significantly reduce the sintering time compared to conventional methods for producing raw solid electrolytes and / or coated solid electrolytes. For example, the method as defined herein based on the rapid heating method can effectively reduce the sintering time from several hours (about 12 hours for conventional solid-state synthesis) to several seconds (e.g., less than about 25 seconds), thereby significantly reducing lithium loss and effectively merging grains into higher material quality.
[0122] The present technology also relates to a coated solid electrolyte obtained by a method as defined herein. Also contemplated is a coated solid electrolyte obtainable by a method as defined herein.
[0123] According to an example, the metal-based coating material can form a uniform coating on the surface of the solid electrolyte. For example, the metal-based coating material can form a substantially uniform metal-based coating on the surface of the solid electrolyte. Alternatively, the metal-based coating material can form a coating on at least a portion of the surface of the solid electrolyte. For example, the metal-based coating can be unevenly dispersed on the surface of the solid electrolyte. According to a related example, the metal-based coating material forms a substantially uniform metal-based coating on the surface of the solid electrolyte.
[0124] According to another example, the metal-based coating material is selected from the group consisting of metal elements, metal alloys, metal oxides, metal fluorides, and combinations of at least two thereof.
[0125] In some examples, the metal-based coating material is a metal element. The metal element can be a metal or a metalloid, such as a metal or a metalloid selected from Al, Cu, Ag, Sn, Sb and Bi. In some related examples, the metal element is Cu, Ag or Sn.
[0126] In other examples, the metal-based coating material is a metal alloy, such as a binary, ternary or quaternary metal alloy. The metal alloy may include a first metal component selected from the 14th and 15th group elements and a second metal component, wherein the second metal component is different from the first metal component. For example, the second metal component can be an alkali metal, an alkaline earth metal, a transition metal, a post-transition metal, a metalloid or a lanthanide. In some related examples, the first metal component is selected from Sn, Sb and Bi, and the second metal component is selected from Al, Mn, Co, Ni, Cu, Ag, Sn, Sb, La, Tb and Bi. Non-limiting examples of metal alloys include Sn-Mn, Sn-Co, Sn-Ni, Sn-Cu, Sn-Cu-Tb, Sn-Ag, Sn-La, Sn-Bi-Ag, Sb-Cu, Sb-Ag and Bi-Ag based alloys. In some related examples, the metal alloy is Cu 3 Sn or Cu 6 Sn 5In other related embodiments, the metal alloy is AgSn x Bi 1-x , wherein x is 0≤x≤1. For example, x may be 1, 0.8, 0.6, 0.4 or 0, and the metal alloy may be selected from AgSn, AgSn 0.8 Bi 0.2 、AgSn 0.6 Bi 0.4 、AgSn 0.4 Bi 0.6 and AgBi.
[0127] In other examples, the metal-based coating material is a metal fluoride, for example, the metal fluoride can be selected from SnF 2 、SnF 4 、ZnF 2 、InF 3 , GaF 3 , SbF 3 , TlF, PbF 2 ,CuF 2 、BiF 3 , AlF 3 , AgF and LiF.
[0128] In other examples, the metal-based coating material is a metal oxide. For example, the metal oxide can be selected from SnO, SnO 2 , CuO, Cu 2 O.Bi 2 O 3 、Al 2 O 3 and Ag 2 O.
[0129] According to another example, the metal-based coating material can be selected based on its melting temperature. For example, at least one component of the metal-based coating material precursor is preferably liquid at the temperature at which the rapid heating method is performed. The metal-based coating material can also be selected based on its ability to chemically react with lithium metal to form a very high lithium conductive phase.
[0130] According to another example, the metal-based coating material optionally further includes at least one doping element, which can be included in a smaller amount, for example, to adjust or optimize its properties. For example, the metal-based coating material can be doped by partially replacing the metal with other elements. For example, the metal-based coating material can be doped with at least one element based on its reduced Li + The doping element is lightly doped with a doping element selected to improve the diffusion barrier capability. For example, the metal-based coating material can be doped with Bi.
[0131] According to another example, the solid electrolyte is in the form of pellets, for example, and the metal-based coating may be deposited on at least a portion of a surface of the solid electrolyte configured to face the negative electrode of the electrochemical cell.
[0132] According to another example, the solid electrolyte may be a glass or ceramic solid electrolyte, preferably a ceramic solid electrolyte. For example, the solid electrolyte may be a garnet-type solid electrolyte. Non-limiting examples of garnet-type solid electrolytes include Li 7 La 3 Zr 2 O 12 (LLZO), Li 6.25 Al 0.25 La 3 Zr 2 O 12 (Al-LLZO), Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 (LLZTO), Li 6.35 Al 0.05 La 3 Zr 2 Ta 0.5 O 12 (Al-LLZTO), Li 6.25 Nd 3 Zr 1.5 Ta 0.5 O 12 (LNZTO), Li 6.25 Sm 3 Zr 1.5 Ta 0.5 O 12 (LSZTO) and Li 6.25 (Sm 0.5 La 0.5 ) 3 Zr 1.5 Ta 0.5 O 12 (LSZTO). For example, the garnet electrolyte is selected from Li 7 La 3 Zr 2 O 12 (LLZO), Li 6.25 Al 0.25 La 3 Zr 2 O 12 (Al-LLZO), Li 6.5 La 3 Zr 1.5 Ta 0.5 O12 (LLZTO) and Li 6.35 Al 0.05 La 3 Zr 2 Ta 0.5 O 12 (Al-LLZTO).
[0133] Depending on the desired final composition of the garnet-type solid electrolyte, the oxide precursor used to prepare the garnet-type solid electrolyte can be a single metal oxide, such as Li 2 O, ZrO 2 、 2 O 5 、Al 2 O 3 、Nd 2 O 3 、Sm 2 O 3 and La 2 O 3 , or bimetallic oxides such as LiZrO 3 、LiLaO 3 、LiNdO 2 、LiSmO 2 、LiTaO 3 ,La 2 Zr 2 O 7 ,La 0.6 Sm 1.4 O 3 and AlLiO 2 , or trimetallic oxides such as Li 7 La 3 Zr 2 O 12 , Li 7 Nd 3 Zr 2 O 12 , Li 5 La 3 Ta 2 O 12 , LiLa 2 TaO 6 、LaZrTa 3 O 11 、LaNdZr 2 O 7 ,La 0.25 Sm 0.25 Zr 0.5 O 1.75 and Li 0.5 La 2 Al 0.5 O4 , or the oxide precursor may be a combination thereof.
[0134] According to another example, the solid electrolyte optionally further comprises at least one additional component or additive, such as an ion conductive material, an inorganic particle, a glass or a ceramic particle; for example, a nanoceramic (e.g., alumina (Al 2 O 3 ), titanium dioxide (TiO 2 ), silicon dioxide (SiO 2 ) and other similar compounds), etc. For example, the additional components or additives can be selected from crystalline and / or amorphous forms of NASICON, LISICON, thio-LISICON, garnet, sulfide, sulfide-halide, phosphate, thiophosphate and combinations thereof. In one example, the additional components or additives are substantially dispersed in the electrolyte. Alternatively, the additional components or additives can be in a separate layer.
[0135] According to another example, the solid electrolyte optionally further includes a second coating material, and the second coating material forms a second coating. If present, the second coating material can be deposited on at least a portion of the opposite surface of the solid electrolyte. It is to be understood that the second coating is deposited on at least a portion of the surface opposite to the surface of the solid electrolyte on which the metal-based coating is deposited. For greater clarity, if present, the second coating can be deposited on at least a portion of the surface of the solid electrolyte configured to face the positive electrode of the electrochemical cell. For example, the second coating material can be selected based on its ability to improve the interface contact between the positive electrode and the solid electrolyte. For example, the second coating material can be a coating material based on succinonitrile, and optionally further includes a lithium salt, such as lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0136] According to an alternative, the electrolyte may be a polymer-ceramic hybrid solid electrolyte. The polymer-ceramic hybrid solid electrolyte may be a multilayer configuration. For example, the polymer-ceramic hybrid solid electrolyte may include: a solid polymer electrolyte layer (which contains a salt in a solvated polymer) and a ceramic electrolyte layer, and the metal-based coating is deposited on at least a portion of the surface of the ceramic layer. It is understood that the solid polymer electrolyte layer is deposited on the surface opposite to the surface of the ceramic layer on which the metal-based coating is deposited.
[0137] In some instances, the ceramic may be a garnet-type solid electrolyte as defined above. The solid polymer electrolyte may be selected from any known solid polymer electrolyte compatible with various elements of the electrochemical cell. For example, the solid polymer electrolyte may be selected based on its compatibility with lithium and the positive electrode. The solid polymer electrolyte may typically include one or more solid polar polymers and salts, the solid polar polymer being optionally cross-linked. Polyether polymers may be used, such as those based on polyethylene oxide (PEO), but several other compatible polymers such as polynitrile polymers are also known for preparing solid polymer electrolytes. The polymer may be further cross-linked. Examples of such polymers include star or comb-shaped multi-branched polymers, such as those described in PCT application WO2003 / 063287 (Zaghib et al.).
[0138] For example, the salt may be an ionic salt, such as a lithium salt. Non-limiting examples of lithium salts include lithium hexafluorophosphate (LiPF 6 ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), 2-trifluoromethyl-4,5-dicyanoimidazole lithium (LiTDI), 4,5-dicyano-1,2,3-triazole lithium (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF 4 ), lithium bis(oxalate)borate (LiBOB), lithium nitrate (LiNO 3 ), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium trifluoromethanesulfonate (LiSO 3 CF 3 )(LiTf), fluoroalkyl lithium phosphate Li[PF 3 (CF 2 CF 3 ) 3 ](LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF 3 ) 4 ](LiTFAB), Lithium Bis(1,2-benzenediol(2-)-O,O')borate Li[B(C 6 O 2 ) 2 ](LiBBB) and combinations thereof.
[0139] The present technology also relates to an electrochemical cell comprising a negative electrode, a positive electrode and a coated solid electrolyte as defined herein.
[0140] According to one example, the metal-based coating of the coated solid electrolyte faces the negative electrode.
[0141] According to another example, if present, the second coating material of the coated solid electrolyte faces the positive electrode.
[0142] According to another example, the solid polymer electrolyte of the coated solid electrolyte faces the positive electrode, if present.
[0143] According to another example, the negative electrode (counter electrode) includes an electrochemically active material, which can be any known material and is selected based on its electrochemical compatibility with the various elements of the electrochemical cell defined herein. Non-limiting examples of electrochemically active materials of the negative electrode include alkali metals, alkaline earth metals, alloys containing at least one alkali metal or alkaline earth metal, non-alkali metals and non-alkaline earth metals, or alloys or intermetallic compounds. According to a related example, the electrochemically active material of the negative electrode can be lithium metal or its alloys.
[0144] According to another example, the positive electrode includes an electrochemically active material, which can be any known material and is selected based on its electrochemical compatibility with the various elements of the electrochemical cell defined herein. The electrochemically active material of the positive electrode can be in the form of particles. Non-limiting examples of electrochemically active materials include metal oxides, lithium metal oxides, metal phosphates, lithium metal phosphates, titanates, lithium titanates, metal fluorophosphates, lithium metal fluorophosphates, metal oxyfluorophosphates, lithium metal oxyfluorophosphates, metal sulfates, lithium metal sulfates, metal halides (such as fluorides), lithium metal halides (such as fluorides), sulfur, selenium, and a combination of at least two of them. For example, the electrochemically active material of the positive electrode can be selected from metal oxides, lithium metal oxides, metal phosphates, lithium metal phosphates, and a combination of at least two of them. For example, the metal of the electrochemically active material may be selected from titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), chromium (Cr), copper (Cu), antimony (Sb), zirconium (Zr), zinc (Zn), niobium (Nb), and a combination of at least two thereof when applicable. According to some related examples, the electrochemically active material of the positive electrode may be lithium iron phosphate (LiFePO 4 , abbreviated as LFP) or lithium nickel manganese cobalt oxide (LiNiMnCoO 2 , abbreviated as NMC).
[0145] According to another example, the electrochemically active material of the positive electrode may also be further doped with other elements or impurities with lower content, for example, to adjust or optimize its electrochemical properties. For example, the electrochemically active material of the positive electrode may be doped by partially replacing the metal with other elements. For example, the electrochemically active material of the positive electrode may be doped with a transition metal (e.g., Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, or Y) and / or a non-transition element (e.g., Mg, Al, or Sb).
[0146] According to another example, the electrochemically active material of the positive electrode can be in the form of particles (e.g., microparticles and / or nanoparticles), which may be newly formed or from commercial sources, and may further include a coating material. The coating material may be an electronically conductive material, for example, the coating may be a carbon coating.
[0147] According to another example, the positive electrode as described herein further optionally includes an electronically conductive material. Non-limiting examples of electronically conductive materials include carbon black (e.g., Ketjen TM black and Super P TM ), acetylene black (such as Shawiniganblack and Denka TM black), graphite, graphene, carbon fiber (such as vapor grown carbon fiber (VGCF)), carbon nanofiber, carbon nanotube and a combination of at least two thereof. According to some related examples, the electronic conductive material can be Super P TM .
[0148] According to another example, the positive electrode as described herein further optionally includes a binder. For example, the binder can be selected based on its compatibility with the various elements of the electrochemical cell. Any known compatible binder is considered. For example, the binder can be a polyether polymer binder, a fluorinated polymer or a water-soluble binder. According to one example, the binder is a fluorinated polymer, such as polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE). According to another example, the binder is a water-soluble binder, such as styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), hydrogenated NBR (HNBR), epichlorohydrin rubber (CHR) or acrylate rubber (ACM), optionally including a thickener, such as carboxymethyl cellulose (CMC), or an acidic polymer, such as poly (acrylic acid) (PAA), poly (methacrylic acid) (PMMA) or a combination thereof. According to another example, the binder is a polymeric polyether binder; for example, a linear, branched and / or crosslinked binder based on polyethylene oxide (PEO), poly(propylene oxide) (PPO) or a combination of the two (or EO / PO copolymers), which optionally includes crosslinkable units. According to a related example, the binder is PVDF. According to another related example, the binder includes succinonitrile (SN), a conductive lithium salt (LiTFSI) and polyacrylonitrile (PAN).
[0149] According to another example, the positive electrode as described herein further optionally includes at least one additional component or additive, such as an ion conductor, an inorganic particle, a glass or ceramic particle, a nanoceramic (e.g., alumina (Al 2 O 3 ), titanium dioxide (TiO 2 ), silicon dioxide (SiO2 ) and other similar compounds), salts (e.g., lithium salts) and other similar components. For example, the additional component can be an ion conductor selected from crystalline and / or amorphous forms of NASICON, LISICON, sulfo-LiSICON, garnet, sulfide, sulfur halide, phosphate and thiophosphate, and a combination of at least two thereof.
[0150] The technology also relates to a battery pack comprising at least one electrochemical cell as defined herein. For example, the battery pack can be a lithium battery pack or a lithium ion battery pack, a sodium battery pack or a sodium ion battery pack, a magnesium battery pack or a magnesium ion battery pack, or a potassium battery pack or a potassium ion battery pack. According to a related example, the battery pack is a lithium battery pack or a lithium ion battery pack. According to another related example, the battery pack is an all-solid-state battery pack.
[0151] According to another example, the metal-based coating as defined herein can substantially stabilize the interface between the negative electrode and the solid electrolyte. In addition, the substantially uniform morphology and lithiophilic nature of the metal-based coating can significantly reduce or even eliminate the interfacial resistance, such that even at 20 mA cm -2 The substantially uniform coating of the metal-based coating material on the surface of the solid electrolyte and the easy lithium diffusion through the metal-based coating can significantly improve the electrochemical performance. For example, the metal-based coating can significantly improve the cycling capability.
[0152] In order to fully unleash the potential of solid electrolytes, the interfacial resistance between the solid electrolyte and the negative electrode should be significantly reduced. Three prerequisites need to be met to eliminate the interfacial resistance: (i) the lithium diffusion through the interfacial layer should be much faster than in the bulk solid electrolyte so that the lithium diffusion resistance in the interfacial layer is essentially negligible; (ii) the interfacial layer should be uniformly coated on the surface of the solid electrolyte to provide a uniform distribution of local current density across the interface during lithium plating / stripping; and (iii) the solid electrolyte should be chemically and electrochemically stable to the interfacial layer (Chen, Wan-Ping et al., "Bridging interparticle Li +conduction in a soft ceramic oxide electrolyte." Journal of the American Chemical Society 143, no. 15 (2021): 5717-5726). For example, many elemental metals or their alloys meet the first requirement because they generally have a high diffusion rate when they form an alloy with a lithium metal anode. However, there is a lack of effective and scalable methods to uniformly coat ultrathin layers of metals or metal alloys onto the surface of solid electrolytes. Previous studies used mechanical spreading or sputtering methods to form interfacial layers on solid electrolytes, which are highly uncontrollable and generally produce a large number of uncoated areas, so that despite the surface modification, there is interfacial resistance. In addition, the reported interfacial resistance still exhibits 5 to 150 Ω cm when using different metal coating strategies. -2 This indicates that completely eliminating such interfacial resistance is still a challenge.
[0153] The melt quenching method as described herein can be used to apply a zero resistance metal-based interface layer coating to the surface of a solid electrolyte. The melt quenching method as described herein uses a rapid heating / cooling device and can be used to form a metal-based material in situ and apply it to the surface of a solid electrolyte. A wide range of metals with binary and ternary compositions were explored as candidates for the interface layer, and their electrochemical properties were fully evaluated. It was demonstrated that certain metal elements exhibit a synergistic effect in their binary and ternary alloys so that the alloy can be uniformly coated on the surface of the solid electrolyte while providing zero lithium / solid electrolyte interface resistance. Several types of metal alloys (AgSn 0.6 Bi 0.4 O x The most promising one) endows the solid electrolyte with negligible interfacial resistance with the lithium metal anode. Advanced characterization and theoretical calculations were performed to reveal the mechanism of the excellent interfacial stability of this coated solid electrolyte with the lithium metal anode. The obtained results reveal new mechanistic insights that are crucial for the further development of alloy-type interfacial layers.
[0154] Example
[0155] The following non-limiting examples are exemplary embodiments and should not be construed as further limiting the scope of the present invention.These examples are better understood in conjunction with the accompanying drawings.
[0156] Example 1 - Densified Li coated with a layer of metal-based material 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Synthesis of (LLZTO) solid electrolyte
[0157] (a) Solid-state synthesis of densified LLZTO solid electrolyte
[0158] Garnet-type solid electrolytes are prepared by solid-state synthesis and densified by a modified rapid heating method (Wang, Chengwei et al., "A general method to synthesize and sinter bulk ceramics inseconds." Science 368.6490(2020):521-526).
[0159] Three garnet-type solid electrolytes with different compositions were synthesized, namely Li 6.25 Al 0.25 La 3 Zr 2 O 12 (Al-LLZO), Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 (LLZTO) and Li 6.35 Al 0.05 La 3 Zr 2 Ta 0.5 O 12 (Al-LLZTO). The respective precursors lithium hydroxide monohydrate (LiOH·H 2 O), zirconium dioxide (ZrO 2 ), lanthanum oxide (La 2 O 3 ) and tantalum pentoxide (Ta 2 O 5 ) and aluminum oxide (Al 2 O 3 ) are weighed to obtain the desired stoichiometry. For example, LiOH·H 2 O, ZrO 2 ,La 2 O 3 and Ta 2 O 5The precursors were used to prepare LLZTO in a molar ratio of 7.15:1.5:1.5:0.25. The sample was then uniformly mixed by planetary ball milling at 300 rpm for about 10 hours. The resulting mixture was then cold pressed into pellets and then annealed in a muffle furnace at a temperature of about 900°C for about 12 hours. The as-prepared LLZTO pellets were then sandwiched between two graphite heating elements and further densified by rapid heat treatment at a temperature of about 1280°C for about 10 seconds under an argon atmosphere. The densified LLZTO solid electrolyte was then removed from the rapid heating device and stored in an argon-filled glove box.
[0160] (b) Coating a metal-based layer on the surface of the LLZTO solid electrolyte prepared in Example 1(a)
[0161] The garnet-type solid electrolyte prepared in Example 1(a) is coated with a metal-based material layer comprising at least one metal element selected from Group 14 and Group 15 elements and at least one second metal element by two different methods. For example, the metal element selected from Group 14 and Group 15 elements can react with lithium to form a Li conductive compound, and the second metal element can help adjust the melting point and boiling point of the metal alloy so that the alloy remains in its liquid form during heating. In some examples, the metal alloy is further doped with bismuth.
[0162] The surface of the LLZTO solid electrolyte prepared in Example 1(a) was coated with different metal-based materials. The corresponding AgSn, CoSn and CoSn were prepared by weighing the corresponding elemental metal powders and uniformly mixing the powders using a mortar and pestle or a ball mill. 6 、LaSn 2 、MnSn、Ni 2 Sn, AgSb, CoSb, CuSb or AgSn x Bi 1-x (where x = 1, 0.8, 0.6, 0.4 and 0) of the desired stoichiometric metal powder precursors. In order to coat the metal-based material on the surface of the garnet-type solid electrolyte by the melt quenching method, the garnet-type solid electrolyte pellets are rubbed on excess elemental metal powder spread on weighing paper, during which the metal-based particles are attached to the garnet surface via van der Waals forces. Then, an argon jet is used to blow off the free powder from the garnet surface. The LLZTO pellets treated with the metal-based precursor are then sandwiched between two graphite heating elements with the coated side facing up, and the temperature is rapidly raised to approximately 1100°C to melt the metal precursor and allow the liquid metal to spread completely on the LLZTO surface. By heating the sample at approximately 1×10 3 ℃min -1 The cooling rate is fast quenching to obtain a uniform metal-based coating.
[0163] LLZTO powder coated with a metal base material was also prepared by mixing the metal precursor powder with the LLZTO powder at a weight ratio of about 1:40 and then performing the melt-quenching method of this example.
[0164] Example 2 - Characterization of the LLZTO solid electrolyte coated with a layer of metal-based material prepared in Example 1(b)
[0165] The LLZTO solid electrolyte coated with a layer of a metal-based material prepared in Example 1(b) was characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and scanning transmission electron microscopy (STEM).
[0166] (a) X-ray diffraction (XRD)
[0167] The crystal phase and purity of the LLZTO solid electrolyte coated with a layer of metal-based material prepared in Example 1(b) were investigated by XRD. As will be discussed later, the coating may also contain metal oxides (e.g., SnO / SnO 2 and Bi 2 O 3 ), so the total coating composition is then formulated as AgSn 1-y Bi y O x (0≤y≤1, 0≤x≤3). XRD measurements were performed using a Rigaku MiniFlex X-ray diffractometer, and 2θ was 1.5° min -1 The scanning rate is scanned from 10° to 60°. 0.6 Bi 0.4 O x Coated LLZTO solid electrolyte and XRD characterization was performed to confirm the presence of AgSn on the LLZTO surface 0.6 Bi 0.4 O x coating, and the resulting spectrum is shown in Figure 3 The diffraction peaks of the original LLZTO are basically the characteristic peaks of the cubic phase LLZTO. Compared with the XRD spectrum of the original LLZTO, the 0.6 Bi 0.4 O x The XRD spectrum of the LLZTO solid electrolyte can be observed with Ag and Ag 3 Several small peaks corresponding to Sn alloy and Sn-Bi alloy indicate the presence of composite materials of different metal-based materials on the surface of LLZTO.
[0168] (b) X-ray photoelectron spectroscopy (XPS)
[0169] The chemical composition of the LLZTO solid electrolyte coated with a layer of a metal-based material prepared in Example 1(b) was studied by XPS (Kratos Axis Ultra DLD). 0.6 Bi 0.4 O x The coated LLZTO solid electrolyte was loaded into a sealed capsule filled with argon to ensure air-free transfer into the XPS chamber.
[0170] XPS characterization was performed to investigate the composition and thickness of the alloy coating. Figure 4 (a) shows AgSn before and after argon ion sputtering time equal to 600 seconds 0.6 Bi 0.4 O x XPS measurement spectrum of LLZTO solid electrolyte. 0.6 Bi 0.4 O x The XPS spectrum obtained on the outer surface of the coated LLZTO solid electrolyte shows peaks pointing to Ag, Bi, Sn, C and O. The presence of carbon may be the result of a very thin hydrocarbon layer adsorbed on the sample, while the oxygen may come from the oxidation of the metal alloy surface. It should be noted that no obvious peaks of Zr, La and Ta were observed from the spectrum, which means that after surface modification by melt quenching method, the LLZTO surface is uniformly covered with metal alloys. Figure 4 (b) Shown in AgSn 0.6 Bi 0.4 O x XPS deconvoluted composition distributions of Ag, Sn, Bi, La, and Zr at different argon ion sputtering times on the surface coated with LLZTO solid electrolyte. Figure 4 (b) shows that AgSn 0.6 Bi 0.4 O x Surface coated with LLZTO solid electrolyte (region I; Figure 4 (b)) has some residual BiO x SnO x Layer coverage; this SnO-rich x The layer is hereinafter referred to as SnBiO x The convolution refinement XPS spectra of Ag, Sn and Bi in regions I and II were recorded to further investigate the coordination of each element ( Figure 4 (c)). The Sn and Bi atoms in region I are partially bonded with oxygen, so their deconvoluted XPS peaks are split into peaks corresponding to metallic Sn and tin oxide (SnO x ) and metallic Bi and bismuth oxide (BiO xHowever, Ag atoms basically maintain their metallic state, which may be attributed to their oxidation resistance compared with Sn and Bi. AgSn 0.6 Bi 0.4 O x / LLZTO / AgSn 0.6 Bi 0.4 O x EIS measurements of the samples revealed that the interfacial resistance remained unchanged after the electrolyte was exposed to ambient atmosphere for approximately 60 min ( Figure 5 ), which indicates that the basic dense SnBiO x The presence of the layer may be beneficial to protect LLZTO from contact with the atmosphere (e.g., H 2 O and CO 2 ) reaction. x and AgSn 0.6 Bi 0.4 Both are reactive toward lithium metal, which facilitates the wetting of lithium metal on the LLZTO surface ( Figure 6 ), resulting in the elimination of interface resistance. The main body of the alloy coating (region II) consists of Ag, Bi and Sn, and its composition is roughly equivalent to AgSn 0.6 Bi 0.4 , which indicates that AgSn 0.6 Bi 0.4 The layer was successfully coated onto the surface of LLZTO, where each element was evenly distributed. The deconvoluted fine spectra of Sn and Bi in region II show a significant decrease in the intensity of the peaks pointing to the metal oxides compared to the corresponding peaks in region I, indicating that the oxygen content in region II is greatly reduced. After about 200 seconds of argon sputtering, the amount of Zr suddenly increased, indicating that the AgSn was completely removed. 0.6 Bi 0.4 O x coating and exposing the LLZTO surface, which roughly corresponds to an 80nm thick AgSn 0.6 Bi 0.4 O x Coating. (c) Scanning electron microscopy (SEM)
[0171] LLZTO and the AgSn prepared in Example 1(b) were studied by SEM (FEIQuanta 650). 0.6 Bi 0.4 O x Morphology of coated LLZTO solid electrolyte.
[0172] For the original LLZTO and AgSn 0.6 Bi 0.4 O x Coated LLZTO solid electrolyte for measurement. Pristine LLZTO and AgSn 0.6 Bi0.4 O x The SEM images of the coated LLZTO solid electrolyte are shown in Figure 7 (a) to 7(c) and 7(d). Figure 7 As can be seen from (a) to (c), the conventional solid-state process and the subsequent densification step using a rapid heating method ( Figure 2 (b)) results in approximately 60% densification of LLZTO. The original LLZTO solid electrolyte has a clean and smooth surface consisting of interconnected LLZTO grains with well-defined grain boundaries. Figure 7 As can be seen in (d), when AgSn 0.6 Bi 0.4 O x When the AgSn layer is coated on the surface of LLZTO, the surface roughness increases, which can be attributed to the surface being coated with AgSn 0.6 Bi 0.4 O x Layer coverage.
[0173] This is further demonstrated by elemental mapping obtained by scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS) ( Figure 8 and 9 ). Figure 8 and Fig. 9 The AgSn 0.6 Bi 0.4 O x Elemental mapping images of LLZTO solid electrolyte and AgSn coated 0.6 Bi 0.4 O x Cross section of a LLZTO-coated solid-state electrolyte. Figure 8 and Fig. 9 Shows uniform Ag, Sn, and Bi signal distribution over the entire scan area.
[0174] Fig.10 Presentation showing AgSn 0.6 Bi 0.4 O x (a) Low magnification SEM image and (b) high magnification SEM image of the interface between the coated LLZTO solid electrolyte and the lithium metal anode.
[0175] (d) Scanning transmission electron microscopy (STEM)
[0176] The AgSn prepared in Example 1(b) was further characterized by STEM (JEOL NEOARM) equipped with an aberration corrector and operated at 80 kV. 0.6 Bi 0.4 O x Coated with LLZTO solid electrolyte.
[0177] For AgSn 0.6 Bi 0.4 O x The AgSn layer was coated with LLZTO solid electrolyte for atomic resolution STEM characterization. However, due to the limitation of electron beam transmission, it is difficult to directly observe the AgSn layer by STEM. 0.6 Bi 0.4 Therefore, the AgSn prepared in Example 1(b) was instead characterized by STEM. 0.6 Bi 0.4 O x coated with LLZTO nanoparticles because when the pellets were replaced by nanoparticles, the AgSn 0.6 Bi 0.4 O x The general morphology of the coating remains essentially unchanged. Fig.11 (a) shows AgSn 0.6 Bi 0.4 O x Low magnification high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of coated LLZTO nanoparticles. Corresponding elemental mapping image taken in the same area ( Fig.11 (b) shows the uniform distribution of Ag, Sn and Bi on the surface of LLZTO nanoparticles, indicating that AgSn 0.6 Bi 0.4 O x The alloy is uniformly coated on the surface of LLZTO nanoparticles. Fig.11 (c) shows the atomic resolution STEM image obtained to show that AgSn 0.6 Bi 0.4 O x Detailed morphology of coated LLZTO nanoparticles. The atomic arrangement depicts two different types of lattice structures overlapping each other. Fast Fourier transform (FFT) of the image shows similarities to LLZTO and Sn 0.95 Bi 0.05 The corresponding pattern of the alloy, due to its very thin layer on the LLZTO surface, Sn 0.95 Bi 0.05 The XRD diffraction pattern of the alloy cannot be clearly detected. LLZTO has The atomic arrangement basically corresponds to the model cubic LLZO structure ( Fig.11 (d)). By processing their corresponding FFT patterns, the LLZTO and metal alloy phases are further separated in the image. The LLZTO phase is represented by yellow false color, while the metal alloy phase is blue ( Fig.11(e)). The metal alloy phase was found to be in close contact with the LLZTO phase near the surface of the LLZTO particles, which is consistent with the observations obtained by SEM and XPS.
[0178] Example 3 - Electrochemical properties of the garnet-type solid electrolyte prepared in Example 1(b)
[0179] (a) Symmetrical battery configuration
[0180] Symmetrical cells were assembled to evaluate the interfacial stability between lithium metal and LLZTO and coated LLZTO solid electrolytes. Two polished lithium disks with a diameter of 6 mm and a thickness of 200 μm were used as working and counter electrodes. The LLZTO solid electrolyte or coated LLZTO solid electrolyte was sandwiched between the two lithium disks. The average thickness of the LLZTO solid electrolyte or coated LLZTO solid electrolyte was about 800 μm and the diameter was about 8 mm. All cells were assembled in a 2032-type button cell housing in an argon-filled glove box with water and oxygen content less than about 0.1 ppm.
[0181] (b) Electrochemical cell configuration
[0182] Commercially available LiFePO 4 (LFP) or LiNi 0.8 Mn 0.1 Co 0.1 O 2 (NMC 811) as the electrochemically active material for the positive electrode to assemble a solid-state full battery. NMC 811 powder was first dried overnight in vacuum at a temperature of about 200°C. To prepare the composite positive electrode, polyacrylonitrile (PAN, Mw = 150,000, Sigma-Aldrich) blended with succinonitrile (99%, Sigma-Aldrich) plasticizer was used as a lithium ion conductive component to provide high lithium ion conductivity and stable operation to the electrochemical cell. LFP or NMC 811 powder was then mixed with Super P TM Conductive carbon, PAN, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and succinonitrile were mixed in a weight ratio of 64.5:10:10:2:13.5 in N-methyl-2-pyrrolidone (NMP) solvent under continuous stirring for about 24 hours to form a uniform slurry. The cathode slurry thus obtained was then cast onto the surface of an aluminum film using a doctor blade and then vacuum dried overnight at a temperature of about 60°C to obtain a solid cathode film. A 6 mm diameter and a typical mass loading of 5 mg cm were then cut from the cathode thus obtained. -2The disc was prepared and used without any further modification. The LLZTO electrolyte used for the solid-state electrochemical cell is coated with a metal-based material layer on one side, on which a polished lithium metal disc having a diameter of about 6 mm and a thickness of about 200 μm is stacked. In order to reduce the interfacial resistance at the interface between the solid electrolyte and the LFP or NMC 811 positive electrode, the surface of the LLZTO solid electrolyte or the coated LLZTO solid electrolyte facing the NMC 811 positive electrode is coated with a polymer thin layer consisting of 5 wt % LiTFSI / succinonitrile (5 wt % / 95 wt %) on the surface of the LLZTO solid electrolyte or the coated LLZTO solid electrolyte. All of the above components are assembled in a 2032-type button cell housing, and the battery is left to stand for about 24 hours before performing electrochemical measurements.
[0183] (c) Electrochemical impedance spectroscopy (EIS)
[0184] The interfacial resistance between the coated LLZTO and lithium metal was measured by EIS using an electrochemical workstation (Biologic VMP-300). An amplitude of 20 m V was used for the EIS measurement. The frequency used for the EIS measurement was 7 × 10 6 Hz to 1Hz.
[0185] Metal-based coating materials with compositions corresponding to their most thermodynamically stable phases were coated on the LLZTO surface, and the interfacial resistance between the coated LLZTO and the lithium metal electrode was measured. For all types of metal-based coatings, the interfacial resistance was significantly reduced to less than 5Ωcm -2 ( Fig.12 (a)), which is comparable to the reported value of more than 1000 Ω cm for the pristine LLZTO solid electrolyte. -2 Without wishing to be bound by theory, the lithiophilic nature of the metal-based coating material may be one of the most important reasons for the reported low interfacial resistance. Previous studies have shown that interfacial resistances of 10 Ω cm were achieved by coating a lithiophilic metal on a garnet-type solid electrolyte. -2 Up to 200Ωcm -2(Luo, W. et al., "Reducing Interfacial Resistance between Garnet-Structured Solid-State Electrolyte and Li-Metal Anode by a GermaniumLayer." Advanced Materials 29(2017):1606042; Feng, W. et al., "Building aninterfacial framework: Li / garnet interface stabilization through a Cu 6 Sn 5 layer." ACS Energy Letters 4.7(2019):1725-1731). The reason for the significantly reduced resistance obtained for the coated LLZTO may be the significantly more uniform distribution of the metal-based coating material obtained using the melt-quenching method compared to the conventional sputtering technique reported in previous studies, which usually results in uneven coatings.
[0186] like Fig.12 As shown in (b), the metal stoichiometric ratio is MnSn, CoSn 6 The interfacial resistance of the LLZTO coated with a layer of metal-based material of AgSn is completely eliminated, while the metal stoichiometric ratio is Ni 2 Sn and LaSn 2 The LLZTO coated with the metal matrix material layer of the alloy still exhibits a performance of approximately 1Ωcm -2 To about 5Ωcm -2 Interface resistance. Ni 2 Sn and LaSn 2The melting point of the alloy is about 1100°C (Okamoto, H. "Supplemental Literature Review of Binary Phase Diagrams: B-Fe, Cr-Zr, Fe-Np, Fe-W, Fe-Zn, Ge-Ni, La-Sn, La-Ti, La-Zr, Li-Sn, Mn-S, and Nb-Re." Journal of Phase Equilibria and Diffusion 37.5 (2016): 621-634; and Nash, P.he A. Nash. "The Ni-Sn (Nickel-Tin) system." Bulletin of alloy phase diagrams 6.4 (1985): 350-359). Therefore, the incomplete melting and / or Ni 2 Sn and LaSn 2 Incomplete wetting of the alloy coating may be the cause of the interfacial resistance. Nevertheless, it is still confirmed that coating LLZTO with a metal-based coating material by the melt quenching method is effective in reducing the interfacial resistance. To further demonstrate the effectiveness of this coating strategy, LLZTO coated with an antimony-based coating material was prepared using the same method, and the interfacial resistance was also substantially eliminated according to EIS measurements ( Fig.12 (c)).
[0187] (d) Galvanostatic charge-discharge measurements and electrochemical behavior
[0188] The interfacial stability of the coated LLZTO electrolyte was evaluated by galvanostatic charge and discharge tests. -2 At a fixed capacity of 0.5 mA cm -2 Up to 20mA cm -2 The current density was measured on the symmetrical cell prepared in Example 3(a).
[0189] By placing the symmetrical cells at 0.5 mA cm -2 and 1.2 mA cm -2 The long-term interfacial stability of the coated LLZTO electrolyte was measured by cycling at a current density of 2000 h.
[0190] The electrochemical performance of the electrochemical solid-state battery prepared in Example 3(b) was evaluated by conducting constant current charge and discharge tests at various C-rates using a battery tester (Neware).
[0191] One of the main goals of developing LLZTO solid electrolytes is to prevent the formation of lithium dendrites during lithium plating. Although maintaining interfacial contact is crucial for smooth lithium plating, when the current density reaches a limit (where the supply of lithium ions from the electrolyte is insufficient for lithium plating), lithium dendrites are still formed (Brissot, C. et al. "Dendriticgrowth mechanisms in lithium / polymer cells." Journal of power sources 81 (1999): 925-929; and Cheng, Xin-Bing et al., "Toward safe lithium metal anode inrechargeable batteries: a review." Chemical reviews 117.15 (2017): 10403-10473). Therefore, although the interface resistance of the coated LLZTO solid electrolyte is significantly reduced, as Fig.13 As shown in , as the current density of the symmetrical battery increases, a short circuit is still caused. Fig.13 The experimental results of rate performance of symmetrical cells containing LLZTO solid electrolytes coated with metal-based material layers based on Ag-Sn (Ag / Sn: 1 / 1), Co-Sn (Co / Sn: 1 / 6), La-Sn (La / Sn: 1 / 2), Mn-Sn (Mn / Sn: 1 / 1), Ni-Sn (Ni / Sn: 2 / 1), Ag-Sb (Ag / Sb: 1 / 1) and Co-Sb (Co / Sb: 1 / 1) are shown tested at a temperature of 60°C. A rate of 14.6 mA cm-2 was observed with an intermediate layer based on Ag-Sn (Ag / Sn: 1 / 1). -2 The best rate performance of the critical current density is La 2 Sn, MnSn, CoSn 6 、Ni 2 The Sn, AgSb, and CoSb-coated LLZTO electrolytes exhibited 7.0, 2.2, 12.8, 13.0, 6.2, and 9.8 mA cm -2 The different critical current densities brought by different metal matrix compositions may be the result of different lithium diffusion rates and lithiophilicity in the metal matrix coating. Although CoSn provides excellent interfacial contact for LLZTO / Li interface, 6 ,La 2 Sn, MnSn, Ni 2Sn, AgSb and CoSb alloys may have lower lithium diffusion rates, which may lead to insufficient lithium supply during plating at high current density and thus lead to the formation of lithium dendrites and short circuiting of the electrochemical cell. It seems reasonable to think that the best performing coating material (i.e. Ag / Sn:1 / 1) can be further modified to improve lithium diffusion to further enhance its rate performance.
[0192] The metal-based coating of the present specification can also be modified to improve lithium diffusion to further enhance its rate performance. It is reported that vacancies can be created by doping metal alloys with heteroatoms (Shuai, J. et al., "Manipulating the Gevacancies and Ge precipitates through Cr doping for realizing the high-performance GeTe thermoelectric material." Small 16.13 (2020): 1906921; and Zhang, X. et al., "Vacancy manipulation for thermoelectric enhancements in GeTe alloys." Journal of the American Chemical Society 140.46 (2018): 15883-15888), thereby promoting vacancy-mediated lithium diffusion in the alloy (Cui, J. et al., "Rational exploration of conversion-alloying reaction based anodes for high-performance K-ion batteries." ACS Materials Letters 3.4 (2021): 406-413). Bismuth atoms are doped into Ag-Sn binary alloys to form ternary alloys. Test based on AgSn x Bi 1-x materials (where x = 1, 0.8, 0.6, 0.4, and 0), and despite the composition change, the interfacial resistance remains essentially negligible ( Fig.14 (a)). However, with increasing bismuth content at x = 0.6 and 0.8, a significant increase in the critical current density is observed ( Fig.14 (b) to (d)), which can be attributed to the increase in the vacancy concentration that promotes lithium diffusion in the alloy. However, when the bismuth content is further increased, the vacancy concentration decreases due to the presence of less tin than bismuth in the alloy, which in turn leads to a lower critical current density ( Fig.14 (e) and (f)).
[0193] Overall, among all the compositions tested, AgSn 0.6 Bi 0.4 O x The LLZTO-coated solid electrolyte exhibited a high conductivity of 20.0 mA cm at 60 °C. -2 The best rate performance with a critical current density of 1.34 Å was achieved. Such a high critical current density not only exceeds the requirement for stable operation of all-solid-state lithium metal batteries, but is also the highest among all types of batteries with solid electrolytes. 0.6 Bi 0.4 O x The long-term interfacial stability of symmetrical cells coated with LLZTO solid electrolyte is demonstrated to demonstrate the practical usefulness of the modified electrolyte in all-solid-state batteries. -2 At a current density of 1 mAh cm -2 ( Fig.15 (a)) and 0.1 mAh cm -2 ( Fig.15 (b)) due to the high ionic conductivity of LLZTO (about 8×10 -4 S cm -1 ) and AgSn 0.6 Bi 0.4 O x Due to the negligible interfacial resistance between the coated LLZTO solid electrolyte and lithium metal, the symmetric cell exhibits a low lithium plating and stripping overpotential of about 35 mV. Even after operating for more than 2000 h, only a small increase in the overpotential can be observed for the symmetric cell, indicating that the AgSn 0.6 Bi 0.4 O x The coated LLZTO solid electrolyte exhibits excellent stability to lithium metal. -2 and 1mA cm -2 At high current densities of 1 mAh cm -2 ( Fig.14 (g) and 15(c)) and 0.1 mAh cm -2 ( Fig.14 (h) Area capacity test of AgSn 0.6 Bi 0.4 O x The interface stability of the coated LLZTO solid electrolyte with lithium metal. In these symmetric cells, the overpotential initially decreases gradually, which may be attributed to the interfacial activation at high current density. The overpotential stabilizes over time to approximately 73-78 mV for more than 700 hours (at 1 mA cm -2 / 1mAh cm-2 ) and 2000 hours (at 1 mA cm -2 / 0.1mAh cm -2 The results show that AgSn 0.6 Bi 0.4 O x The thin layer can fill the inhomogeneity of the LLZTO surface to bring about significantly more uniform current flow along the surface and high Li at the LLZTO / lithium interface. + Conductivity. In AgSn 0.6 Bi 0.4 O x The alloy formed between the layer and the lithium metal may limit the formation of dendrites. To observe any morphological changes after long-term cycling of lithium plating and stripping, the -2 / 0.1mAh cm -2 340 hours and at 1 mA cm -2 / 0.5mAh cm -2 Lithium and LLZTO / AgSn in a symmetrical cell disassembled after 310 hours 0.6 Bi 0.4 O x SEM images were recorded at the cross section of Fig.16 (a)). Fig.16 (b) to (e) are SEM images showing that lithium is uniformly plated on the LLZTO / AgSn after 1000 cycles. 0.6 Bi 0.4 O x Symmetrical cell tests clearly show that the alloy coating on the surface of the LLZTO solid-state electrolyte can effectively suppress the formation of lithium dendrites and greatly enhance the rate and cycling stability of the solid-state electrolyte when combined with a lithium metal electrode.
[0194] In order to prove that AgSn 0.6 Bi 0.4 O x The practical usefulness of coated LLZTO solid electrolytes to assemble solid-state lithium metal electrochemical cells using NMC as the electrochemically active material of the positive electrode. The key to the stable operation of electrochemical cells is the AgSn 0.6 Bi 0.4 O x The ability of coated LLZTO solid electrolyte to suppress the formation of dendrites during long-term cycling. Different from the poor interfacial contact between LLZTO and lithium ( Fig.17 ), AgSn 0.6 Bi 0.4 O xThis promotes excellent interfacial contact between LLZTO and the lithium metal anode, as confirmed by cross-sectional SEM images ( Fig.10 ). Due to AgSn 0.6 Bi 0.4 O x The excellent interfacial stability between the coated LLZTO solid electrolyte and the lithium metal anode resulted in an electrochemical cell providing approximately 156 mAh g at 0.1C. -1 Excellent reversible lithium storage capacity with a cut-off voltage of 4.1V ( Fig.18 The electrochemical cell maintained approximately 116 mAh g even when tested at a high current density of 1 C at room temperature. -1 Capacity( Fig.18 (b)). The excellent rate performance of the electrochemical cell can be mainly attributed to the reduced lithium plating / stripping overpotential, which leads to low polarization in the electrochemical cell ( Fig.18 More importantly, the electrochemical cell provides stable electrochemical performance at 1C for 1000 cycles with an impressive capacity retention of about 86%, and no short circuit is observed due to the stable interface between lithium metal and solid electrolyte. However, by higher cathode loading (e.g., >5 mg cm -2 ) Further improving the energy density requires a new polymer cathode electrolyte system with high Li+ conductivity and oxidation potential.
[0195] (e) Theoretical calculation
[0196] All theoretical calculations are based on density functional theory (DFT) using the generalized gradient approximation via the Perdew-Burke-Ernzerhof (PBE) functional (Perdew, John P. et al., "Generalized gradient approximation made simple." Physical review letters 77.18 (1996): 3865-3868) and projector augmented wave (PAW) pseudopotentials (Kresse, Georg et al., "From ultrasoft pseudopotentials to the projector augmented-wave method." Physical review b 59.3 (1999): 1758-1775). The Vienna ab initio simulation package (ASP) (Hafner, Jürgen. "Ab-initio simulations of materials using VASP: Density-functional theory and beyond." Journal of computational chemistry 29.13 (2008): 2044-2078) was used to perform the DFT calculations, and the convergence criteria were 10 for electronic self-consistent calculations and Hellmann-Feynman force, respectively. -6 eV and 10 -2 eV The kinetic cutoff energy for plane waves was set to 600 eV. Supercells with a size of 3 × 3 × 3 were constructed for DFT calculations, and a 3 × 3 × 3 supercell with a density of less than 0.1 was used. The reciprocal space was sampled using a Monkhorst-Pack grid with a spacing of 1 / 10 (Pack, James D. et al. "Special points for Brillouin-zone integrations" - a reply." Physical Review B 16.4 (1977): 1748). The diffusion barrier was calculated using the climbed image nudged elastic band (CI-NEB) method, using a force-based optimizer with a convergence criterion of 10 -2 eV (Henkelman, Graeme et al., "Aclimbing image nudged elastic band method for finding saddle points and minimum energy paths." The Journal of chemical physics 113.22(2000):9901-9904).
[0197] As mentioned above, the electrochemical performance shows that doping Bi atoms into the AgSn alloy lattice can significantly enhance the overall lithium diffusion kinetics. Therefore, the enhancement mechanism was investigated. Without wishing to be bound by theory, lithium ion diffusion in the alloy may be mediated by lithium vacancies. Higher vacancy concentrations may lead to faster lithium diffusion rates, and the vacancy formation energy may be a good indicator of vacancy concentration, which can be calculated by DFT according to Eq. 3, where E f represents the vacancy formation energy, y is the amount of lithium atoms removed from the unit cell to create the vacancy, x is the stoichiometric ratio of Sn in the alloy, and E Li is the DFT energy of the lithium atom.
[0198]
[0199] Li 2 AgSn and Li 2 AgSn 0.6 Bi 0.4 The vacancy formation energies of Bi-doped alloys are calculated to be 1.07 eV and 0.97 eV, respectively. The lower vacancy formation energy of Bi-doped alloys may indicate a potentially higher lithium vacancy concentration and a resulting faster lithium diffusion rate. In addition to the vacancy concentration, the lithium diffusion barrier in the alloy lattice may also affect the lithium diffusion rate. Fig.19 As shown in (a), the lithium vacancy diffusion can follow the path of 4a→4c→4a, and the corresponding diffusion energy distribution is calculated. Fig.19 (b) Display Li 2 AgSn and Li 2 AgSn 0.6 Bi 0.4 The diffusion barrier between the two is compared, and when Bi atoms are doped into the alloy, the diffusion barrier is significantly reduced, from 0.182 eV to 0.124 eV. Therefore, the enhanced rate performance obtained with Bi-doped alloys may be the result of a higher concentration of lithium vacancies combined with a lower diffusion barrier.
[0200] Example 4 - Synthesis of a metal alloy coated garnet-type solid electrolyte (a) A layer of a metal-based material is coated on the surface of the garnet-type solid electrolyte prepared in Example 1 (a)
[0201] The surface of the densified garnet-type solid electrolyte prepared in Example 1(a) was coated with various metal-based coating materials by a melt quenching method. The metal powder precursors for the garnet coating include aluminum (Al), tin (Sn), antimony (Sb), bismuth (Bi) and copper (Cu). For the binary metal alloy coating, the two metal powders in the required ratio were evenly mixed by planetary ball milling in isopropanol at 300 rpm for 2 hours and then evaporating the solvent in a vacuum oven for 2 hours. The metal powders were stored in an argon-filled glove box to avoid oxidation. The densified garnet-type solid electrolyte pellets were immersed in an excess of metal powder precursors, during which the metal particles were attached to the garnet surface via van der Waals forces. Then, an argon jet was used to blow off the free powder from the garnet surface. The processed pellets were loaded into a rapid heating system, and both the heating and quenching steps were performed at 3×10 3 ℃min -1 Rapid heating (temperature range of about 700° C. to about 1200° C.) was performed at a ramp rate of 1000° C. for about 3 seconds, after which the coated pellets were quickly transferred to an argon-filled glove box.
[0202] Example 5 - Characterization of the coated garnet solid electrolyte prepared in Example 4 (a)
[0203] The coated garnet-type solid electrolyte prepared in Example 4(a) was characterized by XRD, XPS, SEM, EDS and electrochemical tests. Theoretical calculations were also obtained.
[0204] (a) X-ray diffraction (XRD)
[0205] The phases of garnet pellets and densified garnet-type solid electrolyte with and without metal-based coating were characterized by XRD (Rigaku Miniflex 600).
[0206] (b) X-ray photoelectron spectroscopy (XPS)
[0207] The surface chemistry of the coated garnet-type solid electrolyte was investigated by XPS (Kratos Axis Ultra DLD), and the air-sensitive samples were transferred from an argon-filled glove box to the XPS chamber using a set of chambers and capsules to avoid any contamination from the ambient atmosphere. Prior to XPS characterization, hydrocarbons with a thickness of 1 nm were removed by argon ion sputtering.
[0208] (c) Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS)
[0209] The morphology of the garnet pellets and the densified garnet-type solid electrolyte with and without the metal-based coating was characterized by SEM (FEIQuanta 650). For grain size measurement, the surface of the garnet-type solid electrolyte pellets was polished using 1200 grit sandpaper and then thermally etched at a temperature of 1100°C to expose the grain boundaries.
[0210] EDS elemental mapping was used to characterize the chemical composition and morphology of the surface coating, and the samples were transferred from the argon-filled glove box to the SEM chamber using an anti-air transfer protocol, thereby almost completely preventing the samples from being exposed to air.
[0211] (d) Electrochemical test
[0212] Unless otherwise stated, the thickness of the garnet solid electrolyte pellets used in all electrochemical tests was fixed at approximately 800 μm. + The solid electrolyte pellets were sandwiched between two blocking electrodes, and the Li+ / - conductivity of the electrolyte was measured by EIS (Biologic electrochemical workstation) with an amplitude of 20 mV and a frequency range of 7 MHz to 1 Hz. + Conductive resistance. Li is calculated according to Equation 4 + Conductivity, where σ Li+ It's Li + conductivity, l and A represent the thickness and area of the solid electrolyte pellet, respectively. R is the Li + Conductive resistance.
[0213]
[0214] To measure Li + To calculate the migration number, a symmetrical cell with two lithium disks as the working electrode and the counter electrode was assembled. A bias of 10 mV was applied to the cell, and the Nyquist plots before and after the bias was applied were recorded to measure the change in resistance. Li + Migration number, where t Li+ Represents Li + Migration number, I 0 and I s are the current responses to the bias voltage in the initial state and steady state, respectively (Zugmann, Sandra et al., "Measurement of transference numbers for lithium-ion electrolytes via four different methods, a comparative study." Electrochimica Acta 56.11 (2011): 3926-3933). ΔV represents the amplitude of the bias voltage, R 0 and Rs is the interfacial resistance between the lithium metal electrode and the garnet-type solid electrolyte in the initial state and steady state, respectively, obtained from the Nyquist plot.
[0215]
[0216] Used to measure Li + The interfacial stability between the lithium metal electrode and the garnet-type solid electrolyte was evaluated in the same symmetric cell setup as the migration number. A constant current was applied to the symmetric cell to induce lithium plating / stripping, and the corresponding overpotential was recorded over time.
[0217] Evaluation of surface-modified garnet-type solid electrolytes, lithium metal anodes, and LiFePO 4 Electrochemical performance of all-solid-state Li metal batteries composed of composite cathodes composed of PAN or NMC811 as electrochemically active materials. In order to prepare the composite cathode, PAN blended with succinonitrile plasticizer was used as Li + - Conductive components, which have been shown to provide high Li + Conductivity and stable operation (Lu, Ziheng et al., "Modulating Nanoinhomogeneity at Electrode-Solid Electrolyte Interfaces for Dendrite-Proof Solid-State Batteries and Long-Life Memristors." Advanced Energy Materials 11.16(2021):2003811; and Tran, Hoai Khang et al., "Composite Polymer Electrolytes Based on PVA / PAN for All-Solid-State Lithium Metal Batteries Operated at Room Temperature." ACS Applied Energy Materials 3.11(2020):11024-11035). LFP or NMC powder is mixed with conductive carbon black, PAN, SN and LiTFSI in a weight ratio of 64.5:10:10:2:13.5. The solid mixture is dispersed in anhydrous NMP to form a uniform slurry, which is then cast onto aluminum foil and completely dried under vacuum at a temperature of 60°C to obtain a solid cathode film. The mass loading was then cut from the cathode-coated aluminum foil to be approximately 5 mg cm -2The electrode discs were prepared and used to assemble an all-solid-state Li metal battery pack. For electrochemical cell assembly, one side of the garnet-type solid electrolyte pellets was coated with a layer of a metal-based material as described in Example 4(a), and the other side was coated with a thin solid interface organic layer (5 wt% LiTFSI in SN) to increase the interfacial contact between the positive electrode and the garnet-type solid electrolyte. The garnet-type solid electrolyte pellets were then sandwiched between the positive electrode and the lithium metal negative electrode and assembled in a 2032-type button cell housing for electrochemical testing. All electrochemical tests were performed on a Neware battery test system by constant current charging and discharging at different current densities.
[0218] In order to compare the electrochemical performance, conventional electrochemical cells with liquid electrolyte were also prepared using LFP or NMC 811 as the positive electrode electrochemically active material. The positive electrode was prepared by a similar slurry casting method, while the composition of the positive electrode was changed to 80 wt% LFP or NMC 811, 10 wt% conductive carbon black and 10 wt% polyvinylidene fluoride (PVDF) binder. Celgard TM The cell was assembled with a liquid electrolyte made of a 2400 membrane separator impregnated with 1 M LiPF in a non-aqueous solvent mixture of ethylene carbonate / ethyl methyl carbonate (EC / EMC) (1:1 by volume). 6 solution as a liquid electrolyte.
[0219] (e) Simulation
[0220] All simulations were performed using VASP (Hafner, Jürgen. "Ab-initio simulations of materials using VASP: Density-functional theory and beyond." Journal of computational chemistry 29.13 (2008): 2044-2078), which is based on DFT under the generalized gradient approximation with PBE functionals (Perdew, John P. et al., "Generalized gradient approximation made simple." Physical review letters 77.18 (1996): 3865) and PAW pseudopotentials (Kresse, Georg et al., "From ultrasoft pseudopotentials to the projector augmented-wave method." Physical review b 59.3 (1999): 1758). When the residuals of the electronic self-consistent calculation and the Hellmann-Feynman force are less than 10 - 6 eV and 10 -2 eV The DFT calculations are considered to have converged when . The plane wave is cut off at a kinetic energy of 600 eV and a coefficient with a value less than 0.1 is used. A Monkhorst-Pack grid with a spacing of 1000 nm was used to sample the reciprocal space for all static calculations (Pack, James D. et al. "Special points for Brillouin-zone integrations" - a reply." Physical Review B 16.4 (1977): 1748). To simulate the interaction between metal atoms and the garnet surface at finite temperature, ab initio molecular dynamics (AIMD) was performed according to the same parameters as for the static DFT calculations, except that only gamma points were sampled for the calculations.
[0221] Example 6 - Results and Discussion
[0222] Low porosity and high chemical uniformity are essential for garnet-type solid electrolytes to promote uniform lithium plating and stripping and inhibit dendrite formation in Li metal batteries. Conventional methods such as sintering in a furnace are not only expensive and time-consuming, but also fail to produce high-quality garnet-type solid electrolytes due to the inevitable lithium loss at high temperatures. On the other hand, rapid densification methods are generally preferred, mainly because the above-mentioned lithium loss can be minimized by shortening the sintering duration. In order to synthesize high-quality garnet solid electrolytes for later study of their interfacial properties, a rapid heating method (Wang, Chengwei et al., "A general method to synthesize and sinter bulk ceramics in seconds." Science 368.6490(2020):521-526) was developed based on a high-temperature sintering method to enable the preparation of densified garnet solid electrolytes in seconds ( Figure 2 ).
[0223] During the densification step (at a temperature of about 1280°C for about 10 seconds), white LLZTO pellets ( Fig. 20 (a)) is rapidly transformed into a light grey garnet-type solid electrolyte with a diameter of about 7 mm. Comparison of the luminescence images of the two garnet-type solid electrolytes shows that the densified garnet sample emits deep blue light when excited by ultraviolet radiation with a wavelength of 254 nm, while the garnet-type sample densified by rapid heating completely absorbs the 254 nm ultraviolet light ( Fig. 20 (b)), indicating the high purity and low porosity of the densified garnet-type solid electrolyte (Raukas, M. et al., "Ceramic phosphors for light conversion in LEDs." ECS Journal of Solid State Science and Technology 2.2 (2012): R3168).
[0224] Fig.21 (a), 22(a), and 22(b) present the XRD spectra obtained for LLZTO, Al-LLZO, and Al-LLZTO solid electrolytes before and after densification by rapid heating, respectively, all of which show negligible impurities and all characteristic peaks basically correspond to the standard XRD peaks of cubic phase garnet.
[0225] The rapid densification process prevents grain growth in the garnet-type solid electrolyte, resulting in a much smaller average grain size of about 3.7 μm for LLZTO ( Fig.21(b)), while a slight increase in grain size was observed on the garnet-type samples with Al doping, for example, the grain sizes of Al-LLZO and Al-LLZTO were about 5.2 μm and about 4.0 μm, respectively ( Fig. 22 (c) to (f)). This may be due to the fact that aluminum doping promotes grain fusion. Nevertheless, all garnet-type solid electrolytes synthesized by the rapid heating method have fairly high purity and extremely small porosity, which can adjust the uniform distribution of local current density and prevent the formation and growth of lithium dendrites, and are beneficial to the stability of Li metal batteries. LLZTO was thermally etched at a temperature of about 1100°C for about 12 hours to expose the grain boundaries before SEM characterization.
[0226] The ionic conductivity of LLZTO, Al-LLZO, and Al-LLZTO electrolytes was measured, and the conductivity of LLZTO electrolyte reached 8×10 -4 S cm -1 ( Fig.21 (c)), which is the highest among the three compositions of the electrolyte. It is widely reported that Ta doping promotes the smooth Li + conduction, and the high conductivity of LLZTO electrolyte Li + This is consistent with previous reports (Li, Yutao et al., "Optimizing Li+ conductivity in a garnet framework." Journal of Materials Chemistry 22.30 (2012): 15357-15361).
[0227] Pristine garnet electrolytes suffer from sluggish Li transport across the electrolyte-lithium interface due to poor interfacial contact. + transport, which usually results in high interfacial resistance ( Fig.23 ), making it almost impossible to use directly in Li metal batteries. In order to fully solve the interface problem, a series of Li + Conductive metals and their alloys are selected to find the best candidates that can eliminate the interfacial resistance during the operation of Li metal batteries. There are four general principles for screening: (i) the cost of the metal needs to be reasonably low for practical applications; (ii) the metal should form a thermodynamically stable metal alloy with Li at room temperature to promote Li conversion through alloying-dealloying processes at the electrolyte / lithium interface; + (iii) the metal should have low toxicity to humans and the environment; (iv) the metal should be in its liquid form at the processing temperature (i.e., a temperature of 1100°C) to completely wet and spread over the garnet surface to form a uniform coating.
[0228] like Fig.21As shown in (d), five candidates (Al, Sn, Sb, Bi and Cu) were identified. Ultrathin coatings based on single or binary metals were applied onto the surface of LLZTO by melt quenching method using a rapid heating device ( Figure 2 (a)). The EIS spectra of LLZTO solid electrolyte modified with different metal-based coatings are shown in Fig.21 (e). The EIS results show that the coatings based on Al, Sn, Sb, and Bi significantly reduce the interfacial resistance, while the coating based on Cu shows a negligible effect, which may be attributed to the low solubility of Li in Cu. It is worth noting that the Sn-based coated LLZTO solid electrolyte has the smallest interfacial resistance (35Ωcm) compared with the LLZTO solid electrolytes coated with other metals. -2 When Al is doped into garnet electrolytes, the effect of Sn in reducing the interfacial resistance is severely compromised due to the poor wettability of Sn on Al-rich grain boundaries ( Fig.24 (b)). Therefore, only the characterization and electrochemical properties of LLZTO without Al were studied later. In order to further reduce the interfacial resistance, different compositions of Sn-X binary alloys (X: Al, Cu, Bi and Sb) were tested. Nevertheless, when the coated garnet-type solid electrolyte is combined with a lithium metal electrode, according to the crystallographic database, a thermodynamically stable Li-Sn-X phase is formed only when X=Cu, so the interfacial resistance is basically eliminated only when a Sn-Cu (Cu / Sn=3) based coating is deposited on the LLZTO surface ( Fig.21 (f)). It is believed that this is the first time that a surface coating on a garnet solid electrolyte can achieve substantial elimination of interface resistance. Although the elimination of interface resistance was performed at a heating temperature of 1100°C in the case of Cu / Sn=3, it is speculated that there is a temperature and composition range in which the interface resistance can be eliminated. Fig.21 (g) and 24 (a) present the EIS spectra of the Cu-Sn based coating material (Cu / Sn=3) coated on the LLZTO solid electrolyte prepared with a fixed composition but at different temperatures (at Fig.24(a) shows the EIS spectra of the Cu–Sn-based coating material (Cu / Sn = 6 / 5). For the Cu–Sn-based coating material (Cu / Sn = 3), the interfacial resistance decreases to zero only after the heating temperature reaches above 1000 °C, because a relatively high temperature is a prerequisite for forming such a Cu–Sn-based coating material (Fürtauer, S. et al., "The Cu–Sn phase diagram, Part I: new experimental results." Intermetallics 34 (2013): 142–147). The influence of the composition of the Cu–Sn-based coating material was also investigated, and the interfacial resistance as a function of temperature and composition is shown in Fig.21 (h). The results show that a wide range of temperatures (from about 1050 °C to about 1200 °C) and compositions (6 / 5 < Cu / Sn < corresponding to about 39 wt% to about 62 wt% of Cu) can be used to reduce the interfacial resistance to zero, thus providing high robustness for the practical application of this method. As will be discussed later, the coating is covered by an ultrathin layer of a thin oxide (SnO / SnO 2 ), so the entire coating composition is hereinafter denoted as Cu z Sn y O x (6 / 5 < z / y < 3).
[0229] Cu z Sn y O x The morphology of the surface coating is shown in Fig.25 (a) and 25(b) and characterized by SEM. The morphology of the LLZTO with the Cu z Sn y O x coating at low magnification ([[]] Fig.25 (a)) is almost the same as that of the original LLZTO surface ([[]] Fig.21 (b)). When observed at a higher magnification, it is revealed that the surface of the LLZTO after the melt quenching treatment is covered by a layer of densely packed nanosheets ([[]] Fig.25 (b)), which is different from the smooth surface of the original LLZTO ([[]] Fig.26 (a)). As schematically shown in [[[]] Fig.25 (c), it is proposed that the original micron-sized particles of the Cu–Sn powder ([[]] Fig.26 (b)) melt at high temperature during the melt quenching process. Through the interaction of Li and O from LLZTO with Sn and Cu respectively, the Cu–Sn liquid has a strong affinity for LLZTO to wet and spread over the entire LLZTO surface. Upon cooling, the Cu–Sn liquid easily transforms into solid Cu that uniformly covers the LLZTO surface.z Sn y O x , and the morphology of the nanosheets is attributed to Cu z Sn y O x Crystal growth (Tian, Yanhong et al., "Relationship between morphologies and orientations of Cu 6 Sn 5 grains inSn 3.0 Ag 0.5 Cu solder joints on different Cu pads."Materials characterization 88(2014):58-68). In order to further confirm the Cu z Sn y O x The composition of the coating is Cu z Sn y O x XRD and XPS characterization were performed on the coated LLZTO. Fig.25 As shown in (d), compared with the original LLZTO, in addition to the LLZTO peak, the Cu 6 Sn 5 , β-Sn, Cu, SnO and SnO 2 Several characteristic diffraction peaks. 3 SnO x XPS spectra recorded on coated LLZTO with a lateral resolution of about 100 μm (about 730 LLZTO grains) Fig.25 (e)) only shows the main characteristic peaks corresponding to Sn, Cu and O, while the peak corresponding to LLZTO cannot be detected by surface-sensitive XPS technology, indicating that the surface of LLZTO is completely covered with a basically uniform Cu 3 SnO x The Cu was later removed by sputtering for about 10 seconds. 3 SnO xcoating, which is equivalent to removing a surface coating of about 5 nm thick, and new peaks pointing to La, Zr and Ta from LLZTO appear in the new XPS spectrum (Cheng, Lei et al., "Garnet electrolyte surface degradation and recovery." ACS Applied Energy Materials 1.12 (2018): 7244-7252; and Sharafi, Asma et al., "Impact of air exposure and surface chemistry on Li-Li 7 La 3 Zr 2 O 12 interfacial resistance." Journal of Materials Chemistry A 5.26 (2017): 13475-13487), which further indicates the presence of a thin and substantially uniform Cu on the surface of LLZTO 3 SnO x According to the XPS measurement spectrum, a peak corresponding to oxygen was detected in the coating ( Fig.25 (e)), and further record Sn( Fig.25 (f)) and Cu( Fig.25 (g)) high-resolution energy spectrum to reveal the local coordination of oxygen. It was found that the oxygen was mainly bonded to Sn atoms located on the outer surface of the coating, which is due to the inevitable oxidation of Sn when it comes into contact with the atmosphere. In this experiment, the inevitable exposure of Sn to oxygen during both the alloy powder preparation and the melt quenching step is the cause of the surface oxygen; compared with those coatings obtained in an oxygen-deficient atmosphere, the presence of oxygen molecules (i.e., an oxygen-containing environment) has been shown to improve the wettability and thus uniformity of the liquid metal to the garnet substrate. In addition, such an oxide layer (SnO / SnO 2 , hereinafter referred to as SnO x ) may be beneficial because it effectively isolates the garnet-type solid electrolyte and the underlying metal-based coating from ambient moisture. Fig. 27 As shown in Figure 2, the interfacial resistance of uncoated LLZTO doubles after 15 min of ambient exposure, while that of Cu 3 SnO x The coated LLZTO remained unchanged, indicating that the LLZTO surface was intact after exposure to the same environmental conditions. 3 SnO x The composition distribution of the coated LLZTO is schematically shown in Fig.25 (h): Cu may be included 6 Sn 5Cu of Sn and Cu 3 SnO x A layer of tin oxide was applied substantially uniformly onto the LLZTO surface, while the top of this coating was covered by a thin layer of tin oxide.
[0230] To further understand the formation mechanism of Cu-Sn-based coatings, first-principles calculations were performed at 0 K and finite temperature. One of the most critical factors determining the wetting properties of liquid metal on ceramic substrates is the contact angle, which can be derived from Eqs. 4 and 5, where U LG / 2 and U SL are the energies of m, ∞, and 1 layer of liquid metal adsorbed on the substrate, and cosθ is the contact angle (Tian, Hong-Kang et al., "Computational study of lithium nucleation tendency in Li 7 La 3 Zr 2 O 12 (LLZO) and rational design of interlayer materials to preventlithium dendrites." Journal of Power Sources 392(2018):79-86; and Lu, Jin-You et al., "The evolution in graphitic surface wettability with first-principlesquantum simulations: the counterintuitive role of water." Physical ChemistryChemical Physics 20.35(2018):22636-22644).
[0231]
[0232] Fig.28(a) The calculated adsorption energies vs. number of layers for Sn and Cu are summarized, where the contact angles of Cu and Sn on the LLZTO surface at 0 K are calculated to be 108° and 47°, respectively. If a contact angle less than 90° indicates the ability of the liquid to completely wet the substrate, this calculation shows that Sn easily wets and spreads over the surface of LLZTO during the melt quenching process. Although the contact angle of Cu is slightly above 90° at 0 K, it has been widely reported that the contact angle may decrease significantly with increasing temperature (Russell, Kenneth C. et al., "Theoretical and experimental studies of ceramic: metal wetting." MRS bulletin 16.4 (1991): 46-52), causing the contact angle of Cu to be less than 90° during the melt quenching process. Therefore, for Cu and Cu x Sn y Ab initio molecular dynamics simulations were performed to study the wetting behavior at finite temperature and the results are shown in Fig.28 (b). It can be observed that Cu atoms tend to interact with the LLZTO surface and gradually form a coating over time. This process is accelerated when Cu is mixed with Sn to form an alloy layer on LLZTO, which is consistent with experiments showing that Cu-Sn based coating materials (Cu / Sn=3) are superior to Sn in reducing interface resistance ( Fig.21 There are two main factors that explain the better wetting of the Cu-Sn based coating material (Cu / Sn=3): (i) as shown by its higher mean square displacement, Cu 3 The wetting kinetics of Sn are faster than those of Cu ( Fig.29 (a)); (ii) Cu and Sn atoms are revealed to exhibit strong synergistic effects when interacting with LLZTO. 3 Sn is coated on the surface of LLZTO to reduce Cu 3 The Gibbs free energy of the interface between Sn and LLZTO is ( Fig.29 (b) Sn atoms have a strong tendency to bind to Li, so that the original Li-O bond on the LLZTO surface is weakened. Oxygen atoms have very strong electron-withdrawing ability, and they initially attract electrons from lithium on the LLZTO surface. The weakening of the original Li-O bond leads to less coordinated O, which in turn attracts electrons from Cu and strongly adsorbs Cu atoms to the surface of LLZTO, bringing Cu 3 Significantly better wetting of Sn on the LLZTO surface.
[0233] Similar to previously reported lithium alloying interlayers (Luo, Wei et al., "Reducing interfacial resistance between garnet-structured solid-state electrolyte and Li-metalanode by a germanium layer." Advanced Materials 29.22 (2017): 1606042; and Krauskopf, Thorben et al., "Diffusion limitation of lithium metal and Li-Mg alloyanodes on LLZO type solid electrolytes as a function of temperature and pressure." Advanced Energy Materials 9.44 (2019): 1902568), in LLZTO / Cu z Sn y O x When in contact with the Li metal anode in the battery pack, Cu z Sn y O x The coating undergoes a rapid alloying process with lithium, forming a lithium-rich Cu-Li-Sn ternary system interlayer at the interface between garnet and lithium metal. 2 O) completely eliminates the interfacial resistance, establishes an ultra-stable electrolyte-electrode interface, and provides high lithium-ion conduction through the alloying-dealloying process at the LLZTO / interlayer and Li / interlayer interfaces. z Sn y O x The lithium ion conductivity is the same as that of pristine LLZTO (about 8x 10 -4 S cm -1 and at a temperature of 60°C 7×10 -3 S cm -1 ), strengthens Cu z Sn y O x The interlayer coating does not sacrifice the high ionic conductivity of the garnet electrolyte. To confirm the interfacial stability during electrochemical cell operation, the interface after extensive lithium plating was characterized by SEM and EDS. 3 SnO xCoat the LLZTO solid electrolyte to assemble a lithium symmetric battery, and let the lithium electrode on one side of the solid electrolyte completely peel off and -2 The constant current density is transported to the other side ( Fig.30 ). As confirmed by SEM ( Fig.28 (c) and 28(d)), it was observed that the plated Li and Cu 3 SnO x No visible voids are formed near the newly formed interface between the coated LLZTO solid electrolyte, which is in stark contrast to the poor interfacial contact between Li and pristine LLZTO ( Fig.31 ). Although fresh lithium is extensively plated on LLZTO, Cu 3 SnO x The coating remains basically intact on the LLZTO surface ( Fig.28 (e)), and no significant dissolution of LLZTO into lithium was found ( Fig.28 (f) to 28 (h)), which enhances the stability of LLZTO to lithium (Zhu, Yizhou et al., "Origin of outstanding stability in the lithium solid electrolyte materials: insights from thermodynamic analyses based on first-principles calculations." ACS applied materials & interfaces 7.42 (2015): 23685-23693).
[0234] In order to evaluate the Cu 3 SnO x The stability of the LLZTO solid electrolyte was coated, and symmetric cells were assembled and tested at different current densities and temperatures. 3 SnO xThe critical current density at which significant dendrite growth and short circuit occur in the LLZTO solid electrolyte test (Huang, Xiao et al., "None-mother-powder method to prepare dense Li-garnet solid electrolytes with high critical current density." ACS Applied Energy Materials 1.10 (2018): 5355-5365; and Song, Yongli et al., "Revealing the short-circuiting mechanism of garnet-based solid-state electrode." Advanced Energy Materials 9.21 (2019): 1900671). The assembled symmetric cell maintains its stability with increasing current density until it reaches approximately 3 mA cm at room temperature and 60 ° C, respectively. -2 ( Fig.32 (a)) and about 15.2 mA cm -2 ( Fig.32 (b)) The critical current density. Due to the complete elimination of the interfacial resistance, the critical current density is only affected by the ionic conductivity of LLZTO. The ionic conductivity of the electrolyte increases fourfold at 60 °C compared to room temperature, and the critical current density also increases by about fourfold. It is generally accepted that 3 mA cm -2 The critical current density is crucial for the operation of practical lithium metal batteries with high-energy cathodes (Flatscher, Florian et al., "The natural critical current density limit for Li 7 La 3 Zr 2 O 12 garnets." Journal of Materials Chemistry A 8.31(2020):15782-15788); Therefore, based on Cu as defined herein 3 SnO x The LLZTO-coated all-solid-state Li-metal batteries possess a critical current density that not only meets the requirements for practical applications but is also among the highest reported values for all kinds of solid electrolytes (Table 1).
[0235] Table 1. Comparison of electrochemical performance between different solid electrolytes
[0236]
[0237]
[0238] *PPC: Polypropylene carbonate
[0239] Li / LLZTO / Cu was also tested 3 SnO x The cycling stability of / Li at different current densities and temperatures is shown in Fig.32 (c), 32(d) and 33. Cu with a Cu / Sn molar ratio of 3:1 3 SnO x Coated LLZTO solid electrolyte (LLZTO / Cu 3 SnO x ) can be used in a symmetrical battery at room temperature at 0.2 mA cm -2 and 0.5 mA cm -2 The Cu CuO2O3 was subjected to lithium plating / stripping cycles for more than 4000 h at a current density of 2.40 Å with negligible changes in their overpotential and no signs of internal short circuits, which proves that the CuO2O3 3 SnO x Excellent stability of coated LLZTO solid electrolyte in lithium metal batteries. 3 SnO x The stable overpotential of the coated LLZTO solid electrolyte is in sharp contrast to the continuously increasing overpotential of the pristine LLZTO and Sn-coated LLZTO solid electrolytes ( Fig.34 ). In addition, Cu 6 Sn 5 O x The cycling performance of the coated LLZTO solid electrolyte is similar to that of the Cu 3 SnO x The results for the LLZTO-coated solid electrolyte are essentially the same, which is consistent with their similar EIS spectra, where both show negligible interfacial resistance ( Fig.21 (h)). Also at 60 °C and 4 mA cm -2 The Cu-based 3 SnO x The cycling stability of the symmetrical battery coated with LLZTO solid electrolyte was investigated, and the impedance change over time was further characterized using operando EIS; the results showed that the symmetrical battery could operate stably for 1600 hours without an increase in overpotential ( Fig.32 (d)). The Nyquist plot generated by EIS measurement under working conditions shows 11Ωcm -2 The almost constant resistance of Fig.32(e)), which is also consistent with the stable overpotential.
[0240] The results of symmetric battery experiments show that Cu 3 SnO x The coated LLZTO solid electrolyte has a stable interface with the lithium metal anode and is composed of Cu 3 SnO x Lithium metal batteries composed of LLZTO-coated solid electrolytes have the potential to have excellent stability when combined with high-energy cathodes. 3 SnO x Application of coated LLZTO solid electrolyte in actual battery packs, such as Fig.35 As schematically shown in (a), an all-solid-state lithium metal electrochemical cell is assembled using a composite cathode and a lithium metal anode. Fig.35 (b) shows the EIS spectrum of an all-solid-state electrochemical cell composed of LFP and NMC 811 cathodes at room temperature. The semicircle in the high-frequency region reflects the Li + The bulk ionic resistance caused by conduction, and the semicircle in the mid-frequency region represents the charge transfer resistance of the positive electrode (Kim, Sangryun et al., "A complex hydride lithium superionic conductor for high-energy-density all-solid-state lithium metal batteries." Nature communications 10.1 (2019): 1-9). Obviously, for LFP and NMC 811 electrochemical cells, there is no semicircle in the low-frequency region, indicating that the interface resistance has been basically completely eliminated, which is consistent with the symmetric battery results ( Fig.21 (g)).
[0241] The cycling and rate performance of the electrochemical cell with LFP cathode were tested at room temperature and the results showed that the electrochemical cell could provide 155 mAh g -1 The reversible capacity of the battery was 94.6% with a remarkable initial Coulombic efficiency of 94.6% and an excellent capacity retention of 99% after 100 stable cycles at 0.2C. Fig.36 (a)). Furthermore, despite cycling at a high rate of 1C, the electrochemical cell can retain 80% of its capacity ( Fig.36 (b)), while its charge / discharge overpotential is only slightly increased ( Fig.36 (c)).
[0242] It should be noted that composite cathodes containing active materials and polymer electrolytes are used in electrochemical cells for two main reasons: (i) the polymer electrolyte in the composite cathode promotes better interfacial contact with the LLZTO solid electrolyte to bring better rate performance; (ii) side reactions between the electrolyte and the cathode can be significantly prevented, especially for electrochemical cells with NMC 811 cathodes operating at higher voltages. Due to the absence of side reactions at the cathode / electrolyte interface, all-solid-state electrochemical cells with high-voltage NMC 811 cathodes have excellent cycle stability and initial Coulomb efficiency. As Fig.36 shown in (c), the electrochemical cell exhibits an initial Coulomb efficiency of 85.4%, and it can maintain 74% of its capacity even when cycled at a high rate of 1C. This excellent rate performance of the electrochemical cell is mainly attributed to the resistance-free electrolyte / lithium interface and stable lithium plating / stripping at the anode with low overpotential, which brings a consistent voltage platform for the electrochemical cell. The NMC 811 cathode is well-known to have poor cycle stability due to side reactions with liquid electrolytes when operating at high voltages. Compared with the continuous capacity decay in liquid batteries ( Fig.37 ), the all-solid-state electrochemical cell can provide 94% of its initial capacity after 1000 cycles at 1C for a long time. More importantly, the 1000 stable cycles of the all-solid-state electrochemical cell have an average Coulomb efficiency higher than 99.9%, and no internal short circuit caused by dendritic lithium growth is observed, indicating excellent safety compared with liquid batteries. Due to the high interfacial stability at the interface of the Cu 3 SnO x -coated LLZTO solid electrolyte and the lithium metal anode, the electrochemical performance of the electrochemical cell defined in the present invention herein is one of the best among all reported all-solid-state battery packs (Table 1).
[0243] In summary, the surface of the garnet electrolyte is modified by coating a thin layer of Cu z Sn y O x (6 / 5 < z / y < 1 / 2) to eliminate the interfacial resistance between the solid electrolyte and the lithium metal anode. The mechanism of this coating is systematically studied, and the electrochemical performance of the surface-modified garnet solid electrolyte is comprehensively tested in symmetric and complete electrochemical cells. Four key findings can be summarized as follows:
[0244] (1) A uniform and dense coating of Cu z Sn y O x on the surface of the garnet solid electrolyte can be achieved within seconds by means of the melt quenching method, and the surface-modified garnet electrolyte exhibits negligible interfacial resistance when combined with the lithium metal anode. LLZTO / Cuz Sn y O x At room temperature and 60 ° C, 8.0 x 10 -4 and 7.0x 10 -3 S cm -1 The lithium ion conductivity, electronic conductivity and lithium transference number are 7.0x 10 -8 S cm -1 and 0.99.
[0245] (2) The synergistic effect between Cu and Sn when they interact with the garnet surface at high temperature is revealed to be the main reason for the formation of uniform coatings, and the coatings can be formed over a wide range of Cu-Sn compositions and temperatures.
[0246] (3) Symmetric cells based on surface-modified garnet electrolytes exhibit 3 mA cm-2 at room temperature and 60 °C, respectively. -2 and 15.2 mA cm -2 The critical current density can reach 10 ...
[0247] (4) The all-solid-state electrochemical cell consisting of a surface-modified garnet electrolyte and an NMC 811 cathode can deliver 94% of its initial capacity after 1000 cycles at 1C for a long time, with an average Coulombic efficiency above 99.9%.
[0248] Example 7 - Densified pristine Li obtained by rapid sintering 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Synthesis and characterization of (LLZTO) solid electrolyte
[0249] The pristine garnet-type solid electrolyte can be prepared by the rapid heating method as defined herein. As an example, Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 (LLZTO) was synthesized by Joule heating. In order to obtain a uniform densified electrolyte, a lithium oxide precursor (Li 2 O) instead of conventional lithium metal hydroxide (LiOH) and lithium metal carbonate precursors (LiCO) that are commonly used in the traditional solid-state synthesis of oxide-based solid electrolytes. 2 CO 3 ). LiOH and Li 2 CO 3Gas products can be released during the heat treatment, which leads to the pulverization of the final solid electrolyte and thus hinders its densification; from LiOH and Li 2 CO 3 The gaseous products of the decomposition of the precursors can also corrode the heating element (e.g. graphite) during Joule heating. 2 ZrO 3 ) precursor instead of the conventional zirconium dioxide precursor (ZrO 2 ). 2 ZrO 3 The melting point of the precursor (720°C) and ZrO 2 (2715℃) is much lower than that of the sintering temperature, which means that the sintering temperature and time required are significantly lower. 2 O, ZrO 2 or Li 2 ZrO 3 ,La 2 O 3 and Ta 2 O 5 Weigh to obtain the desired stoichiometry. For example, with Li 2 O, ZrO 2 ,La 2 O 3 and Ta 2 O 5 The precursors were prepared in a molar ratio of 3.57:1.5:1.5:0.25 to prepare LLZTO(Z). 2 O、LiZrO 2 ,La 2 O 3 and Ta 2 O 5 The precursors were prepared with a molar ratio of 2.75:1.5:1.5:0.25 for LLZTO (LZ). The samples were then uniformly mixed by planetary ball milling at 300 rpm for about 10 hours. The resulting mixture was then cold pressed into pellets. The as-prepared precursor pellets were then sandwiched between two graphite heating elements and subjected to rapid thermal treatment at a temperature of about 1200°C for about 10 seconds under an argon atmosphere. The densified LLZTO (Z) and LLZTO (LZ) solid electrolytes were then removed from the rapid heating device and stored in an argon-filled glove box.
[0250] like Fig.38As confirmed by the XRD data presented in , both LLZTO(Z) and LLZTO(LZ) solid electrolytes exhibit a substantially high purity phase without any signs of impurities. The SEM images of LLZTO(Z) and LLZTO(LZ) solid electrolytes show that LLZTO(LZ) has a larger grain size (about 7.5 μm) compared to the grain size of LLZTO(Z) (about 4.1 μm); the larger grain size of LLZTO(LZ) is apparently due to the LiZrO used to synthesize LLZTO(LZ). 2 Sintering temperature and ZrO used to synthesize LLZTO(Z) electrolyte 2 The EIS measurements of LLZTO(LZ) and LLZTO(Z) solid electrolytes show 5.9×10 -4 S cm -1 and 2.5×10 -4 S cm -1 Li + Conductivity. LLZTO (LZ) has a higher Li + The electrical conductivity is due to the larger grain size and thus lower number of grain boundaries, which can translate into lower grain boundary resistance and higher Li + Conductivity.
[0251] A one-step synthesis method for synthesizing garnet-type solid electrolytes from metal oxides as precursors using a Joule heating system has been developed. Compared with conventional synthesis of garnet-type solid electrolytes using furnace synthesis and sintering, this technology significantly reduces manufacturing costs (i.e., time and energy).
[0252] Example 8 - Densified Li coated with metal / metal fluoride composite layer 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Synthesis and characterization of (LLZTO) solid electrolyte
[0253] The densified original LLZTO (LZ) solid electrolyte prepared in Example 7 is coated with a metal-based material layer containing at least one metal element selected from Group 14 and Group 15 elements and at least one metal fluoride having a metal element selected from Group 14 and Group 15 elements. For example, the metal element selected from Group 14 and Group 15 elements can react with lithium to form a Li conductive compound, and the metal fluoride can react with lithium metal to form lithium fluoride (LiF) and a Li conductive compound. LiF is an electronic insulator, and after its formation, it can later act as a filler within the coating and promote Li + conduction and prevent the dissolution of metal elements into the lithium metal anode during cycling.
[0254] As an example, the Sn:SnF ratios of 10:0.5, 10:1, 10:2, 10:3, 10:4, 10:5 (Sn:SnF) were prepared by weighing the corresponding powders and uniformly mixing the powders using a mortar and pestle or a ball mill. 2 ) weight ratio of Sn metal powder and SnF 2 mixture of precursors. The coating was applied to the surface of the LLZTO (LZ) pellets prepared in Example 7. In order to coat the metal-based material on the LLZTO (LZ) surface by a melt quenching method, the LLZTO (LZ) pellets were rubbed on excess coating precursor powder spread on weighing paper, during which the metal particles and metal fluoride particles were attached to the garnet surface via van der Waals forces. Then, an argon jet was used to blow off the free powder from the garnet surface. The LLZTO (LZ) pellets treated with the metal-based precursor were then sandwiched between two graphite heating elements with the coated side facing up, and the temperature was rapidly raised to approximately 1100°C and maintained at this temperature for approximately 3 seconds to melt the metal precursor and allow the liquid metal to spread completely on the LLZTO (LZ) surface. By quenching the sample at approximately 1×10 3 ℃min -1 The cooling rate is fast quenching to obtain a uniform metal-based coating.
[0255] The different Sn-SnF prepared in Example 8 were characterized by EIS measurements. 2 -Interface resistance of coated LLZTO (LZ) solid electrolyte. Fig.41 The results show that the interface resistance increases from Sn:SnF 2 10:0.5(15.6Ω) down to Sn:SnF 2 10:3(<1Ω), then increase to Sn:SnF 2 13.1Ω at 10:5, indicating the composition is Sn:SnF 2 The 10:3 coating has the lowest interfacial resistance with the lithium metal anode. 2 Li / Sn-SnF 2 -LLZTO(LZ)-Sn-SnF 2 / Li, the critical current density at which significant dendrite growth and short circuit occur was tested. 2 The critical current density of 5.8 mA cm was observed for the (10:3) interlayer. -2 The best rate performance ( Fig.42 ); and coated with Sn:SnF 2 (10:0.5), Sn:SnF 2 (10:1), Sn:SnF 2 (10:2), Sn:SnF 2(10:4), Sn:SnF 2 The solid-state electrolysis of LLZTO (LZ) with a ratio of (10:5) showed 1.0, 3.0, 3.4, 3.6, and 2.6 mA cm -2 The critical current density.
[0256] Many modifications may be made to any of the embodiments described above without departing from the scope of the invention.Any reference, patent or scientific literature mentioned in this application is hereby incorporated by reference in its entirety for all purposes.
Claims
1. A method for producing a coated solid electrolyte comprising a metal-based coating deposited on at least a portion of a surface of the solid electrolyte, the method comprising the steps of: (i) depositing a precursor powder of a metal-based coating material on at least a portion of a surface of a solid electrolyte; (ii) subjecting a precursor powder of a metal-based coating material to a rapid heating method to produce a molten metal-based coating material; and (iii) solidifying the molten metal-based coating material to produce the coated solid electrolyte.
2. The method according to claim 1, wherein step (i) is performed by a mechanical or chemical coating method.
3. The method according to claim 2, wherein step (i) is performed by a powder deposition technique.
4. The method according to claim 3, wherein the powder deposition technique is a powder spreading technique, a powder friction technique or a powder dipping technique.
5. The method according to any one of claims 1 to 4, further comprising the step of removing excess precursor powder of the metal-based coating material before step (ii).
6. The method according to any one of claims 1 to 5, wherein the rapid heating method is selected from the group consisting of Joule heating, microwave radiation, spark plasma sintering, induction heating, laser sintering, infrared radiation and electric pulse consolidation. The method according to claim 6 , wherein the rapid heating method is a Joule heating method.
8. The method according to any one of claims 1 to 7, wherein the rapid heating method is carried out for a time of less than about 90 s, or less than about 80 s, or less than about 70 s, or less than about 60 s, or less than about 50 s, or less than about 40 s, or less than about 30 s, or less than about 25 s, or less than about 20 s, or less than about 15 s, or less than about 10 s.
9. The method according to any one of claims 1 to 7, wherein the rapid heating method is performed for a time of about 1 s to about 90 s, or about 1 s to about 80 s, or about 1 s to about 70 s, or about 1 s to about 60 s, or about 1 s to about 50 s, or about 1 s to about 40 s, or about 1 s to about 30 s, or about 1 s to about 25 s, or about 1 s to about 20 s, or about 1 s to about 15 s, or about 1 s to about 10 s, or about 2 s to about 10 s, or about 3 s to about 10 s.
10. The method according to any one of claims 1 to 9, wherein the rapid heating method is carried out at a temperature in the range of about 550°C to about 1400°C, or about 600°C to about 1350°C, or about 650°C to about 1300°C, or about 700°C to about 1250°C, or about 700°C to about 1200°C.
11. The method according to any one of claims 1 to 10, wherein the rapid heating method is carried out at about 5×10 2 ℃min -1 to about 1.44×10 4 ℃min -1 The heating temperature is carried out within a range of ramp rates.
12. The method according to claim 11, wherein the rapid heating method is performed at about 3×10 3 ℃min -1 The heating temperature is ramped at a rate of 1.
13. The method according to any one of claims 1 to 12, wherein step (iii) is carried out at a concentration of about 5×10 2 ℃min -1 to about 4.8×10 3 ℃min -1 The cooling temperature is ramped within a range of rates.
14. The method of claim 13, wherein step (iii) is performed at a concentration of about 3×10 3 ℃min -1 The cooling temperature is ramped at a rate of 1.
15. The method according to any one of claims 1 to 14, further comprising the step of preparing a solid electrolyte.
16. The method according to any one of claims 1 to 15, further comprising the step of densifying the solid electrolyte.
17. The method of claim 16, wherein the densification step is performed by a rapid heating method.
18. The method according to claim 17, wherein the rapid heating method is selected from the group consisting of Joule heating, microwave radiation, spark plasma sintering, induction heating, laser sintering, infrared radiation and electric pulse consolidation.
19. The method of claim 18, wherein the rapid heating method is Joule heating.
20. A coated solid electrolyte obtained by the method according to any one of claims 1 to 19.
21. The coated solid electrolyte according to claim 20, wherein the metal-based coating is uniformly deposited on the surface of the solid electrolyte.
22. The coated solid electrolyte according to claim 20, wherein the metal-based coating is unevenly dispersed on the surface of the solid electrolyte.
23. The coated solid electrolyte according to any one of claims 20 to 22, wherein the metal-based coating material is selected from metal elements, metal alloys, metal oxides, metal fluorides, and a combination of at least two thereof.
24. The coated solid electrolyte according to claim 23, wherein the metal-based coating material is a metal element.
25. The coated solid electrolyte according to claim 24, wherein the metal element is selected from Al, Cu, Ag, Sn, Sb and Bi.
26. The coated solid electrolyte according to claim 25, wherein the metal element is Cu, Ag or Sn.
27. The coated solid electrolyte according to claim 23, wherein the metal-based coating material is a metal alloy.
28. The coated solid electrolyte according to claim 27, wherein the metal alloy is a binary, ternary or quaternary metal alloy.
29. A coated solid electrolyte according to claim 27 or 28, wherein the metal alloy comprises a first metal component selected from metal elements of Groups 14 and 15 of the Periodic Table and a second metal component, wherein the second metal component is different from the first metal component.
30. The coated solid electrolyte according to claim 29, wherein the first metal component is selected from Sn, Sb and Bi.
31. The coated solid electrolyte according to claim 29 or 30, wherein the second metal component is an alkali metal, an alkaline earth metal, a transition metal, a post-transition metal, a metalloid or a lanthanide.
32. The coated solid electrolyte of claim 31, wherein the second metal component is selected from Al, Mn, Co, Ni, Cu, Ag, Sn, Sb, La, Tb and Bi.
33. The coated solid electrolyte according to any one of claims 27 to 32, wherein the metal alloy is Sn-Mn, Sn-Co, Sn-Ni, Sn-Cu, Sn-Cu-Tb, Sn-Ag, Sn-La, Sn-Bi-Ag, Sb-Cu, Sb-Ag or Bi-Ag based alloy.
34. The coated solid electrolyte according to claim 33, wherein the metal alloy is Cu3Sn or Cu6Sn5.
35. The coated solid electrolyte according to claim 33, wherein the metal alloy is AgSn x Bi 1-x , where x is 0≤x≤1.
36. The coated solid electrolyte according to claim 35, wherein the metal-based coating is selected from AgSn, AgSn 0.8 Bi 0.2 、AgSn 0.6 Bi 0.4 、AgSn 0.4 Bi 0.6 and AgBi.
37. The coated solid electrolyte according to claim 23, wherein the metal-based coating material is a metal fluoride.
38. A coated solid electrolyte according to claim 37, wherein the metal fluoride is selected from SnF2, SnF4, ZnF2, InF3, GaF3, SbF3, TlF, PbF2, CuF2, BiF3, AlF3, AgF and LiF.
39. The coated solid electrolyte according to claim 23, wherein the metal-based coating material is a metal oxide.
40. The coated solid electrolyte according to claim 39, wherein the metal oxide is selected from SnO, SnO2, CuO, Cu2O, Bi2O3, Al2O3 and Ag2O.
41. The coated solid electrolyte according to any one of claims 20 to 40, wherein the solid electrolyte is a ceramic solid electrolyte.
42. The coated solid electrolyte according to claim 41, wherein the ceramic solid electrolyte is a garnet-type solid electrolyte.
43. The coated solid electrolyte according to claim 42, wherein the garnet solid electrolyte is selected from Li7La3Zr2O 12 (LLZO), Li 6.25 Al 0.25 La3Zr2O 12 (Al-LLZO), Li 6.5 LqCy 1.5 Ta 0.5 O 12 (LLZTO), Li 6.35 Al 0.05 La3Zr2Ta 0.5 O 12 (Al-LLZTO), Li 6.25 Nd3Zr 1.5 Ta 0.5 O 12 (LNZTO), Li 6.25 Sm3Zr 1.5 Ta 0.5 O 12 (LSZTO) and Li 6.25 (Sm 0.5 La 0.5 )3Zr 1.5 Ta 0.5 O 12 (LSZTO).
44. The coated solid electrolyte according to claim 43, wherein the garnet solid electrolyte is selected from Li7La3Zr2O 12 (LLZO), Li 6.25 Al 0.25 La3Zr2O 12 (Al-LLZO), Li 6.5 LqCy 1.5 Ta 0.5 O 12 (LLZTO) and Li 6.35 Al 0.05 La3Zr2Ta 0.5 O 12 (Al-LLZTO).
45. The coated solid electrolyte according to any one of claims 20 to 44, further comprising at least one additional component.
46. The coated solid electrolyte of claim 45, wherein the additional components are selected from ion conductors, inorganic particles, glass or ceramic particles, nanoceramics, salts and other similar additives.
47. A coated solid electrolyte according to claim 45 or 46, wherein the additional component is dispersed within the electrolyte material.
48. A coated solid electrolyte according to claim 45 or 46, wherein the additional component is in a separate layer.
49. The coated solid electrolyte according to any one of claims 20 to 48, further comprising a second coating material deposited on at least a portion of the opposite surface of the solid electrolyte.
50. The coated solid electrolyte of claim 49, wherein the second coating material is a succinonitrile-based coating material.
51. The coated solid electrolyte of claim 50, wherein the succinonitrile-based coating material comprises a lithium salt.
52. An electrochemical cell comprising a negative electrode, a positive electrode and the coated solid electrolyte according to any one of claims 20 to 51.
53. The electrochemical cell of claim 52, wherein the metal-based coating of the coated solid electrolyte faces the negative electrode.
54. The electrochemical cell of claim 52 or 53, wherein the second coating material of the coated solid electrolyte, if present, faces the positive electrode.
55. The electrochemical cell of any one of claims 52 to 54, wherein the negative electrode comprises an electrochemically active material comprising an alkali metal, an alkaline earth metal, an alloy containing at least one alkali metal or alkaline earth metal, a non-alkali metal and a non-alkaline earth metal, or an alloy or an intermetallic compound.
56. The electrochemical cell of claim 55, wherein the electrochemically active material of the negative electrode comprises lithium metal or an alloy thereof.
57. The electrochemical cell of any one of claims 52 to 56, wherein the positive electrode comprises an electrochemically active material.
58. The electrochemical cell of claim 57, wherein the electrochemically active material of the positive electrode is selected from the group consisting of metal oxides, lithium metal oxides, metal phosphates, lithium metal phosphates, titanates, lithium titanates, metal fluorophosphates, lithium metal fluorophosphates, metal oxyfluorophosphates, lithium metal oxyfluorophosphates, metal sulfates, lithium metal sulfates, metal halides (e.g., fluorides), lithium metal halides (e.g., fluorides), sulfur, lithium sulfur, selenium, lithium selenium, and a combination of at least two thereof.
59. The electrochemical cell of claim 58, wherein the metal of the electrochemically active material is selected from titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), zirconium (Zr), zinc (Zn), niobium (Nb), and a combination of at least two thereof.
60. The electrochemical cell of any one of claims 57 to 59, wherein the positive electrode further comprises at least one electronically conductive material.
61. The electrochemical cell of claim 60, wherein the electronically conductive material is selected from the group consisting of carbon black, acetylene black, graphite, graphene, carbon fibers, carbon nanofibers, carbon nanotubes, and combinations of at least two thereof.
62. The electrochemical cell of any one of claims 57 to 61, wherein the positive electrode further comprises at least one binder.
63. The electrochemical cell of claim 62, wherein the binder is selected from the group consisting of a polyether type polymer binder, a fluorinated polymer, and a water soluble binder.
64. The electrochemical cell of any one of claims 57 to 63, wherein the positive electrode further comprises at least one additional component.
65. The electrochemical cell of claim 64, wherein the additional components are selected from ionic conductors, inorganic particles, glass or ceramic particles, nanoceramics, salts, and other similar additives.
66. A battery comprising at least one electrochemical cell according to any one of claims 52 to 65.
67. The battery of claim 66, wherein the battery is selected from the group consisting of a lithium battery, a lithium ion battery, a sodium battery, a sodium ion battery, a potassium battery, a potassium ion battery, a magnesium battery, and a magnesium ion battery.
68. The battery of claim 66 or 67, wherein the battery is selected from a lithium battery and a lithium ion battery.
Citation Information
Patent Citations
Highly-stable polymeric electrolyte and use thereof in electrochemical systems
WO2003063287A2
Cited By
Surface modified Li3InxGa1-xCl6 material, preparation thereof and application of surface modified Li3InxGa1-xCl6 material in lithium metal solid-state battery
CN120117647A
Surface-modified Li3In x Ga 1-x Cl6 material, its preparation and application in lithium metal solid-state batteries
CN120117647B